Lightweight real-time detection of sweet potato virus disease by a hybrid CNN–Transformer network - Ru Han; Lei Shu; Grzegorz Cielniak; Yan Zhu; Xing Yang; Fan Yang; Kai Huang (Computers and Electronics in Agriculture, 2026)

TGF-β-induced autophagy in pulmonary artery endothelial cells associated with chronic thromboembolic pulmonary hypertension - Ying-Ju Lai; Yen-Lin Huang; Ching-Yen Tsai; Po-Ru Chen; Chi-Jen Chang; Yung-Hsin Yeh; Celina De Almeida; Hsao-Hsun Hsu (Journal of Molecular Medicine, 2026)

Characterization of hygroscopicity-based mixing state at four sites in China - Jingye Ren; Fang Zhang; Lu Chen; Jieyao Liu; Wei Xu; Honghao Xu; Zhe Wang; Ru-Jin Huang (Journal of Aerosol Science, 2026)

Polymer-specific oxidative biotransformation of polyethylene and polypropylene microplastics by the stored-grain pest Tribolium castaneum - Sakhawat Shah; Jin-Ru Zhao; Ze-Yu Liu; Yi-Jia Chen; Jie Tang; Karam Khamis Elgizawy; Qiu-Ying Huang; Elvis Genbo Xu; Feng-Lian Yang (Chemical Engineering Journal, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Reconstruction and projection of the evolution of Schiaparelli Glacier, Southern Patagonia (1749–2100) using OGGM constrained by dendroglaciological records - Yafan Hu; Ru Huang; Haifeng Zhu; Xiaolong Zhu; Jussi Grießinger; Eryuan Liang; David Farías-Barahona; Ilaria Tabone; Wolfgang Jens-Henrik Meier (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

O-B modified starch emulsions as novel additives enhancing 3D printing adaptability and quality of Dosidicus gigas surimi gels - Luhan You; Kaina Duan; Yi Hu; Jie-Ting Geng; Wenge Yang; Tao Huang; Ru Jia (Innovative Food Science & Emerging Technologies, 2026)

Novel electrochemical sensor for histamine: enhancing food safety with polydopamine-modified crystalline NCU-1 zincophosphate material - Asit Kumar Panda; Yu-Chung Chang; Murugan Thiruppathi; Chun-Ru Hsu; Ching-Ping Lu; Yu-Ru Huang; Ja-an Annie Ho; Chih-Min Wang (Food Research International, 2026)

Structural and functional responses of myofibrillar proteins from yellow croaker to plasma-activated buffer: evidence from a simulated PAW system - Fangqi Yuan; Quanyou Guo; Zuofeng Shi; Huawei Wu; Wenge Yang; Tao Huang; Ru Jia; Huamao Wei (Food Research International, 2026)

Incorporation of nanoscale fishbone enhances frozen snakehead fish slice quality via synergistic mechanisms: Pickering emulsion oxygen barrier and TGase-mediated protein crosslinking - Ziaur Rahman; Liangzi Zhang; Yajin Zhang; Arsalan Khan; Junaid Khan; Soottawat Benjakul; Qilin Huang; Shanbai Xiong; Juan You; Ru Liu; Dan Jia; Tao Yin (Food Chemistry, 2026)

Drought sensitivity analysis of Persian oak based on stable carbon isotopes from the Zagros Mountains, western Iran - Mohsen Arsalani; Jussi Grießinger; Ru Huang; Achim Bräuning (European Journal of Forest Research, 2026)
Drought-resilient native tree species are becoming increasingly vulnerable to the intensifying impacts of climate change. In this study, we conducted the first tree-ring stable carbon isotope and intrinsic water-use efficiency (iWUE) study of annually separated tree rings of Persian oak ( Quercus brantii Lindl.) covering the period 1953–2022. The study sites are located at three different elevations in the Zagros Mountains. δ 13 C chronologies at all sites showed higher (less negative) δ 13 C values during the major drought events of 1964, 1984, and 2007–2008, followed by corresponding increases in their respective iWUE values. The highest iWUE values were observed at the high-elevation site. iWUE at the mid and high-elevation sites showed a pronounced increase from 2008 to 2022, suggesting a common physiological response of trees to increasing water limitation. Correlations with climate variables revealed significant negative relationships between winter and spring precipitation and δ 13 C, at mid and high-elevation sites. All three sites exhibited negative correlations with the Palmer Drought Severity Index (PDSI) and the Standardized Precipitation-Evapotranspiration Index (SPEI) at accumulation periods ranging from 1 to 12 months, confirming the high sensitivity of Persian oak to hydroclimatic conditions during both the previous and current growing seasons, with particularly strong correlations observed at the mid and high-elevation sites. These patterns highlight the dominant role of drought in regulating stomatal conductance and carbon uptake, providing physiological evidence relevant to the observed oak dieback phenomena in the Zagros Mountains. Overall, δ 13 C variations in Persian oak are primarily driven by hydroclimatic factors (precipitation, relative humidity, and vapor pressure deficit), with timing and strength of these parameters varying in space and time among all studied sites. Our findings reveal that Persian oak exhibits different adaptive physiological strategies across the altitudinal transect, shifting from conservative water-use behaviour in more arid environments (low and high-elevations) to more flexible gas-exchange regulation under mesic conditions (mid elevations).

Analyzing phosphorus flow in crop production via interpretable machine learning: Insights from a typical agricultural region of Jiangxi Province, China - Yuejin Chen; Wending Huang; Lele Ru; Shuhui Peng; Wuhu Guo; Evgeny Abakumov; Ekaterina Chebykina; Yalan Zhang; Zanxu Chen; Dan Wang; Shijie Dai; Yanqi Liu; et al. (Applied Geochemistry, 2026)

Adaptive genetic trade-offs govern the enantioselective degradation and horizontal transfer of ibuprofen catabolic genes - Weihao Zhu; Mingli Jiang; Rui Fan; Kaihua Pan; Shenghao Wang; Lu Huang; Qiantong Ru; Yinhu Jiang; Qian Li; Qian Zhu; Mingliang Zhang; Zhijian Ke; et al. (Journal of Hazardous Materials, 2026)

A core innate immune gene panel derived from germ-free larval zebrafish transcriptomics resolves strain-specific induction by Aeromonas veronii and Lacticaseibacillus rhamnosus GG - Xiang-Ru Liu; Ying Liu; Chen-Cong Zhang; Zi-Shu Huang; Feng-Yi Guo; De-Sheng Pei (Fish & Shellfish Immunology, 2026)

Diniconazole leads to neurotoxicity in zebrafish via triggering TLR4/MyD88-mediated immune-inflammatory responses - Hongying Zhang; Ru Guo; Youjuan Wu; Jiajun Huang; Zijia Yin; Kaiwen Zhao; Xuefeng Liu; Meifeng Li; Zeyin Jiang; Shanghong Wang; Lihua Fan; Chengyu Hu; et al. (Fish & Shellfish Immunology, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Heterolytic urea exchange-mediated thermal locking: Architecting 3D printed photo-mechanochromic smart elastomers - Min Yu; Yeting Huang; Dong Wang; Ru Song; Hanzhao Gong; Shuming Zhang; Xiaoyu Han; Yangzheng Li (Chemical Engineering Journal, 2026)

A comparative observational study of prokaryotic microbial community dynamics across different Litopenaeus vannamei cultivation systems - Chaosheng Zhou; Yue Wu; Maocang Yan; Rongmao Lu; Xiaolin Huang; Shaoguo Ru (Frontiers in Marine Science, 2026)
Introduction Microbial communities are key indicators of ecosystem health in aquaculture, yet their temporal dynamics under different cultivation systems remain poorly characterized. This study compares prokaryotic community succession across three commercial Litopenaeus vannamei cultivation systems with contrasting pond construction, salinity, and water-exchange intensity. Methods We collected 85 water samples from five sub-ponds per system at 15-day intervals and characterized prokaryotic communities via 16S rRNA amplicon sequencing, combined with α/β diversity, LEfSe, and PICRUSt2-based functional analyses. Results Community composition and diversity differed markedly among systems: α-diversity was highest in the earthen brackish pond (EBXS) and lowest in the concrete seawater pond (HSDT). Proteobacteria dominated all systems, while Actinobacteria prevailed in EBXS, which also showed increasing relative abundances of potentially pathogenic genera (Aeromonas, Mycobacterium, Rickettsia) over time. HSDT exhibited the highest predicted metabolic potential (90 enriched KEGG pathways). Temporally, EBXS displayed more stable succession and higher overall similarity, whereas high-level ponds showed greater species turnover. Discussion Salinity and cultivation system emerged as major correlates of community variation, though inherently confounded in our observational design. These patterns suggest a trade-off between community stability and pathogenic risk across production strategies. Our findings offer empirical baselines and testable hypotheses for future controlled studies to disentangle the individual effects of salinity, pond construction, and water management on microbial assembly in aquaculture systems.

Role of pickering emulsions in enhancing the preservability and functionality of protein gel systems: a structured review with bibliometric analysis - Ramy M. Khoder; Arsalan Khan; Ziaur Rahman; Nayyar Iqbal; Qilin Huang; Juan You; Mahmoud Salah; Ibrahim Khalifa; Tao Yin; Ru Liu (Critical Reviews in Food Science and Nutrition, 2026)

Facial width-to-height ratio predicts aggression and contest outcomes in wild golden snub-nosed monkeys - Pei Zhang; Yan-Ni La; Fei Niu; Jin-Bang Zhang; Paul A. Garber; Derek W. Dunn; Ru-Liang Pan; Kang Huang; Bao-Guo Li (Animal Behaviour, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Changes in source-specific health risks of PM2.5-bound trace elements after the residential “coal-to-gas” conversion measure in urban Beijing - Wei Yuan; Ru-Jin Huang; Jing Duan; Jie Guo; Wenjuan Cao; Ting Wang; Jingye Ren; Yanan Zhan; Wei Xu (Journal of Environmental Sciences, 2026)

Rubidium isotopes reveal no sub-arc melting of altered oceanic crusts in a cold subduction zone - Zi-Qiang Zhong; Ding-Sheng Jiang; Saskia Erdmann; Yi-Xiang Chen; Xia Hu; Zheng Xu; Wei Zhang; Jia-Ru Sheng; Wang-Ye Li; Fang Huang (Geochimica et Cosmochimica Acta, 2026)

Food-Derived Phycocyanin from Spirulina Promotes Longevity and Lipid-Metabolic Transcriptional Remodeling in Caenorhabditis elegans - Siang-Ru Huang; Yoshikazu Nishikawa; Jiue-in Yang; Hiroshi Tanaka; Chih-Jen Lai; Chien-Sen Liao (Food Bioscience, 2026)

LncRNA WFDC21P mediates the tobacco carcinogen induced malignant transformation of human normal lung epithelial cells by regulating tumor stemness - Shengsheng Li; Ru Liu; Shiyao Ye; Yitong Li; Linhan Huang; Qiuxian Wan; Zhuolin Liu; Yibo Wu; Nuoyan Wang; Minmin Huang; Jianjun Wu (Food and Chemical Toxicology, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

Enhanced photocatalytic fuel cell performance via C/WO3/ZnFe2O4 ternary photoanode for simultaneous wastewater degradation and energy harvesting - Yi Xiao; Ru Zhang; Qi Feng; Hailong Gao; Jiawei Ma; Ting Wu; Yongkui Huang; Longjun Xu; Chenglun Liu (Journal of Environmental Management, 2026)

Effects of salinity and fermentation time on the microbial community, flavor, and metabolites of shrimp paste - Jing-ru Chen; Jia-bo Huang; Jing Li; Shi-meng Sun; Peng-fei Jiang (Food Research International, 2026)

Shifting carbon emission dominance across subway lifecycle phases: A refined subsystem-interaction assessment - Jing Pu; Chen Cai; Shijun Chen; Ru Guo; Ruimin Lin; Xingyu Ding; Jia Liu; Kaiming Peng; Xiangfeng Huang (Environmental Impact Assessment Review, 2026)

Knowledge-infused hierarchical causal inference framework for decoding sludge settleability to quantitatively regulate multi-process wastewater treatment - Yucheng Li; Chen Cai; Feiyun Sun; Xiangfeng Huang; Kaiming Peng; Ru Guo; Jia Liu (Bioresource Technology, 2026)

Synergistic effects of phenylsilane and isopropyl titanate-modified montmorillonite nanofillers on the thermal and flame-retardant properties of PVA films - Jing-Yao Xiao; Lei Huang; Shi-Xiang Xiong; Jian-Feng Lan; Ru-Xin Chen; Long-Long Jin; Ze-Chao You; Bai-yi Chen; Xian-Hui Zhang (Applied Clay Science, 2026)

Water use complementarity in old-growth mixed forests versus competition in younger successional mixed forests - Ru Huang; Wolfgang Jens-Henrik Meier; Achim Bräuning; Peili Fu; Zexin Fan; Sugam Aryal; Mohsen Arsalani; Haifeng Zhu; Chenxi Xu; Eryuan Liang; Shalik Ram Sigdel; Jussi Grießinger (Agricultural and Forest Meteorology, 2026)

Correction to: Engineered Alzheimer Organoids Validate the Link Between Intracellular and Soluble p-Tau Biomarkers and Highlight the Contribution of Astrocytic Tau - Ru Zhang; Xiaoxu Dong; Gang Pei; Shichao Huang (Neuroscience Bulletin, 2026)

A regional classification framework integrating AI and causal inference revealing the drivers of lake eutrophication in China - Yong Xu; Ru-Long Ma; Yu-Xi Feng; Bin Zou; Shen-Xin Li; Wen-Ting Huang; Shang-Chen Zhou; Wen-Qiang Peng (Water Research, 2026)

Mobility heterogeneity influences the relationship between built environment and metro travel emissions - Jing Pu; Chen Cai; Wei Zhu; Quan Yuan; Ru Guo; Xingyu Ding; Jia Liu; Kaiming Peng; Yanei Xue; Xiangfeng Huang (Transportation Research Part D: Transport and Environment, 2026)

Wavelength-tunable light regulates binding affinity of histone deacetylase inhibitors via azobenzene Photoswitches - Yifan Ru; Sifan Guo; Yu He; Xiujuan Huang; Zhenguo Zhang; Lei Shi; Xiaoguang Shao; Zhong Li; Wen Fu; Xusheng Shao (Pesticide Biochemistry and Physiology, 2026)

Towards an integrated framework for prioritized management of soil heavy metals: Industrial imprints, dispersion, and geological amplification - Qingxin Deng; Jin-Ru Feng; Hong-Gang Ni; Kefeng Huang; Maohai Jiang (Journal of Environmental Chemical Engineering, 2026)

Mask-CDKD: A source-free and label-free cross-domain knowledge distillation framework from SAM for satellite onboard VHR land-cover mapping - Daoyu Shu; Zhan Zhang; Xiao Huang; Ru Wang; Nan Jia; Xinzhe Fu; Bingnan Yang; Fang Wan; Jianzhong Lu; Jianya Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Carboxymethylated PGA/ASK composite: Synergistic mechanism for stabilizing protein network and improving freeze resistance of shrimp gel - Kaina Duan; Zijing Liu; Luhan You; Jie-ting Geng; Wenge Yang; Huamao Wei; Tao Huang; Ru Jia (Innovative Food Science & Emerging Technologies, 2026)

Ratio limitation of burnt-bitter-aroma compounds in strong-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Zheng-Juan Zhu; Jing Luo; Ling Xiang; Yan-Hong Xiang; Song-Tao Wang; Wen-Wen Zhang; Qing-Qing Liu; Ting Huang; Zheng-Hong Xu; Yong-Jun Yuan (Food Chemistry, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Enhancing camptothecin biosynthesis in Camptotheca acuminata through CrLAMT transfer from Catharanthus roseus - Ru Huang; Wen-Hui Ma; Bing-Run Yang; Fang Yu; Ping Kou (Biotechnology Letters, 2026)

Harnessing Rhizopus oligosporus mycelium as a sustainable protein source: Functional properties and optimization of a meat-analogue “chicken popcorn” - Bao-Hong Lee; Ru-Yi Ferng; Hao-Yuan Chien; Cheng-Hao Huang; Wei-Hsuan Hsu (Food Hydrocolloids, 2026)

A tree-ring-based early summer precipitation reconstruction since 1720 CE on the southeastern Tibetan Plateau - Min Cai; Ru Huang; Haifeng Zhu; Lazhu; Wolfgang Jens-Henrik Meier; Jussi Grießinger (Dendrochronologia, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

Engineered Alzheimer Organoids Validate the Link Between Intracellular and Soluble p-Tau Biomarkers and Highlight the Contribution of Astrocytic Tau - Ru Zhang; Xiaoxu Dong; Gang Pei; Shichao Huang (Neuroscience Bulletin, 2026)

A scaling-constrained symbolic intelligence approach for parameterizing submesoscale vertical heat transport - Bingzheng Yan; Junyi Wang; Ru Chen; Shan Huang; Tianmu Zheng; Kun Gao (Ocean Modelling, 2026)

Sugar profile in monofloral honeys from China: Implications for quality control - Ru Jia; Sha Yan; Xuezhe Huang; Zongyan Cui; Xiaofeng Xue (Food Chemistry, 2026)

A facile identification strategy for coffee variety via the machine learning-assisted nanozyme sensor array - Jie Li; Xingna Zheng; Siyu Wang; Yi Ru; Yongxin Li; Hui Huang (Food Control, 2026)

Validation of a numerical model for seismic behavior of wind turbine nacelle components using experimental data - Wei-Hung Hsu; Bai-Yi Huang; Juin-Fu Chai; Fan-Ru Lin (Engineering Structures, 2026)

Assessing synergy of CO2 and pollutant reductions in industrial parks from the industrial chain perspective - Shenghua Yan; Chen Cai; Jia Liu; Kaiming Peng; Ru Guo; Xiangfeng Huang (Environmental Impact Assessment Review, 2026)

Dual-functional eggshell-derived system for comprehensive phosphorus recovery from agricultural wastewater: From laboratory validation to pilot-scale implementation - Qiao Wu; Maoqing Fan; Xiaoyu Zheng; Ming Zeng; Saihong Ru; Chengyou Sun; Chao Huang (Bioresource Technology, 2026)

Remote impacts of maritime continent deforestation on early summer precipitation across Asia - Chiung-Wen June Chang; Wan‑Ru Huang; Yi-Chieh Chen; Suranjith Bandara Koralegedara (Climatic Change, 2026)
Deforestation in the Indo-Pacific Maritime Continent (MC) has intensified in recent decades, yet its remote impacts on Asian monsoon precipitation remain inadequately understood. Using idealized land-use perturbation experiments with the Community Earth System Model, we demonstrate that MC deforestation reorganizes early-summer (May–June) precipitation across Asia through large-scale circulation changes. Our results show that Meiyu precipitation, the early-summer rainy season along the subtropical East Asian coastal zone (SEAC), is suppressed by strengthened subsidence and column drying, whereas precipitation over the Indian Peninsula increases under enhanced ascent and vertically integrated moisture-flux convergence. Precipitation characteristics also shift regionally: the SEAC exhibits simultaneous reductions in both frequency and intensity, the Indian Peninsula shows increases in both metrics, and the MC itself experiences fewer but more intense events. A joint frequency–intensity analysis reveals that these precipitation patterns reflect regional thermodynamic and dynamic controls, where reduced near-surface humidity and equivalent potential temperature suppress event initiation, while elevated values facilitate initiation, and variations in column moisture and moisture-flux convergence regulate precipitation intensity. Collectively, these results identify a land-use–driven teleconnection through which localized deforestation in the MC remotely modulates regional circulation and Meiyu precipitation, highlighting the central role of tropical land–atmosphere coupling in shaping Asian hydroclimate variability.

Recent understanding of crosstalk between muscle and different organs in regulating freshwater fish flesh quality under stress condition: A review - Liwen Wu; Liangzi Zhang; Ling Peng; Yong Long; Guili Song; Soottawat Benjakul; Juan You; Ru Liu; Qilin Huang; Huawei Ma; Dan Jia; Tao Yin (Aquaculture, 2026)

Transcriptomic reveals the acute exposure of ammonia nitrogen on muscle quality in fish: the coupling effect of acidity, thermal, and salinity - Ling Peng; Tao Yin; Shanbai Xiong; Juan You; Ru Liu; Qiling Huang; Soottawat Benjakul; Dan Jia (Aquaculture, 2026)

Causal-informed domain adaptation with cross-attention for predicting anomalous effluent quality fluctuations in wastewater treatment plants - Hanxin Zhang; Haiping Zhang; Jia Liu; Kaiming Peng; Ru Guo; Feiyun Sun; Xiangfeng Huang; Chen Cai (Water Research, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

The variations of the North African monsoon precipitation over the past 200 years - Sainan Liu; Ru Huang; S.-Y. Simon Wang; Chenxi Xu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Exploratory analysis of epigenetic dynamics and small extracellular vesicles in Penaeus vannamei hemocytes under inactivated Vibrio parahaemolyticus priming - Yu-Ru Lin; Guan-Lin Lai; Yu-Hsuan Sun; Ta-Jeng Yang; Ting-Yu Huang; Huu-The Nguyen; Muhammad Ar Rozzaaq Nugraha; Novi Rosmala Dewi; Yeh-Fang Hu; Fan-Hua Nan (Journal of Invertebrate Pathology, 2026)

Temperature-driven regime shifts in riverine bacterial communities: Machine learning identifies key thresholds and seasonal management implications - Ru Liu; Peng Wang; Wang Shu; Mingjun Ding; Minghua Nie; Gaoxiang Huang; Hua Zhang; Qinwei Chen; Wei Yang (Journal of Environmental Sciences, 2026)

LC-MS-based non-targeted metabolomics analysis of sea urchin during frozen storage under different packaging methods - Jia-bo Huang; Yi-hui Tang; Jing Li; Jing-ru Chen; Peng-fei Jiang (Food Chemistry, 2026)

Mechanism of the influence of single-phase dynamic gelation process on the structure and properties of bigels - Yanlei Gao; Qing Xiong; Shilin Zhao; Qilin Huang; Yang Hu; Ru Liu (Food Hydrocolloids, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

Selective enrichment of nitrogen-metabolizing species in agricultural small water bodies: the potential regulation of additives from microplastics color - Qian Zhang; Xinhui Huang; Hongyu Shan; Peizhao Li; Jin Cui; Lishan Zhang; Shan Zhong; Xuan Ru; Zongchen Li; Xiaohua Shu (Bioresource Technology, 2026)

Tracking the dynamic changes in vegetation belts in China: spatiotemporal insights into climate and human influences - Yong Xu; Yun-Gui Lu; Qiang-Yu Dai; Wen-Ting Huang; Shang-Chen Zhou; Ru-Long Ma; Wen-Qiang Peng; Yu-Xi Feng (Regional Environmental Change, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

Coconut shell pyrolysis oil: dual-pathway approach to antioxidants and renewable aromatic biofuels - Ru Sun; Jincheng Zhang; Meng Sun; Xinghua Liu; Dan Qian; Ping Huang (Fuel, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Mechanisms and Scenario Predictions of the Digital Economy’s Impact on Pollution and Carbon Emission Reduction: A Case Study of the Yellow River Basin in China - Tianle Shi; Zhengmeng Hou; Jianhua Liu; Hao Fang; Qichen Wang; Yilin Guo; Ru Zhang; Liangchao Huang (International Journal of Environmental Research, 2026)
This study investigates how the digital economy reduces pollution and carbon emissions (RPCE) in the Yellow River Basin through three core mechanisms: (1) enabling real-time environmental monitoring and precision regulation, (2) fostering enterprise green production via digital transformation, and (3) driving technological innovation and industrial upgrading, proposing three testable hypotheses on these pathways. Indicators for the digital economy and RPCE are developed, and a spatiotemporal analysis of RPCE levels is conducted at both the municipal and grid scales. Employing the STIRPAT (Stochastic Impacts by Regression on Population, Affluence, and Technology) model to comprehensively examine population, affluence, and technology drivers, and innovatively integrating analysis at both municipal and grid scales to overcome traditional limitations, this study examines the direct and mediating effects of the digital economy on RPCE, along with heterogeneity analysis, endogeneity discussions, and exogenous shock tests, providing a more refined framework for revealing the mechanisms. Based on empirical findings, future RPCE trends in the basin are projected, with a proposed three-pronged strategy: digital infrastructure deployment, sector-specific interventions, and place-based prioritization (technology-upgrading midstream; clean-energy transition upstream). The main conclusions are as follows: (1) During the study period, RPCE in the Yellow River Basin showed significant improvement, with an upstream > downstream > midstream pattern and a block-like distribution. (2) The statistically significant regression coefficient (β = -0.476, p < 0.01) indicates a positive impact of the digital economy on RPCE, thus validating Hypothesis 1. Both technological innovation and industrial structure upgrading serve as positive mediators in the influence of the digital economy on RPCE, confirming Hypotheses 2 and Hypotheses 3. (3) The growth rate of population size is a major factor driving divergence in the RPCE index across the basin. To advance RPCE in the Yellow River Basin, policies should prioritize the development of the digital economy while promoting high-quality economic growth and stabilizing population growth rates.

Optimizing the spatial configuration of scallop suspended cultivation net cages by leveraging seston flux variables based on the lattice Boltzmann hydrodynamics - Gangqin Tu; Haifei Liu; Zhiming Ru; Tao Sun; Wei Yang; Wei Huang; Li Cheng (Aquaculture, 2026)

Spatio-seasonal distribution, precursor transformation, and ecological risks of per- and polyfluoroalkyl substances in port sediments: Insights from a subtropical urban harbor - Chih-Feng Chen; Noralyn G. Dimaongon; Yun-Ru Ju; Chiu-Wen Chen; Yee Cheng Lim; Ming-Huang Wang; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Integrated assessment of trace element enrichment and accumulation in estuarine sediments of southwestern Taiwan using Sr/Ba ratios and pollution indices - Chih-Feng Chen; Noralyn G. Dimaongon; Yee Cheng Lim; Ming-Huang Wang; Yun-Ru Ju; Kent Naiah D. Araña; Chiu-Wen Chen; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Biofilm-mediated mitigation of nitrous oxide emissions in anammox-based wastewater treatment - Zhiman Lin; Jinfan Zhang; Ru Wang; Jingmin Ou; He Zhang; Zihua Wang; Fangyuan Zheng; Xiantao Sun; Xin Wei; Yiming Huang; Zhenguo Chen; Mark C.M. van Loosdrecht; et al. (International Biodeterioration & Biodegradation, 2026)

Beyond the treeline: assessing the potential of juniper shrub-ring δ18O for paleoclimatic research in the Himalayas - Wolfgang Jens-Henrik Meier; Jakob Wernicke; Ru Huang; Haifeng Zhu; Sugam Aryal; Jussi Grießinger (Global and Planetary Change, 2026)

Proteomic analysis of exudates reveals the quality of marinated snakehead fish slice as affected by precooling and freezing treatments - Ziaur Rahman; Yajin Zhang; Arsalan Khan; Soottawat Benjakul; Qilin Huang; Shanbai Xiong; Juan You; Ru Liu; Tao Yin (Food Chemistry, 2026)

Food byproduct-derived as sustainable nano-stabilizers for Pickering emulsions influenced by macronutrient composition - Ramy M. Khoder; Mahmoud Abou-Elsoud; Nayyar Iqbal; Ibrahim Khalifa; Juan You; Qilin Huang; Tao Yin; Ru Liu (Food Chemistry, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

Quantitative resolution analysis in seismic imaging: From classical theory to cutting-edge advances - Jidong Yang; Jianping Huang; Hejun Zhu; Jiaxing Sun; Li-yun Fu; George McMechan; Houzhu Zhang; Ru-Shan Wu (Earth-Science Reviews, 2026)

Configurational entropy–induced lattice distortion in high-entropy Prussian blue analogues derived transition metal phosphide accelerates electrocatalytic hydrogen evolution in alkaline media - Yu-Ru Liu; Mia Rinawati; Ping-Chen Shi; Sofiannisa Aulia; Wuttichai Tanmathusorachai; Hsin-Chih Huang; Wei-Nien Su; Ling-Yu Chang; Wei-Hsiang Huang; Min-Hsin Yeh (Chemical Engineering Journal, 2026)

Seasonal and day-night variations in light absorption properties of humic-like substances and effects of aqueous-phase photooxidation - Wei Yuan; Jing Duan; Ting Wang; Yi Liu; Jie Guo; Wenjuan Cao; Ru-Jin Huang (Atmospheric Research, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Sustainable design and application of recyclable dialkylimidazolium dimethylphosphate ionic liquids for green cellulose fiber processing - Hui-Wen Hsu; Shih-Huang Tung; Ru-Jong Jeng (Sustainable Chemistry and Pharmacy, 2025)

An intelligent and active polyvinyl alcohol hydrogel packaging incorporating alizarin and Zn-MOF for shrimp freshness monitoring and preservation - Min Zhang; Enguang Zuo; Xiaoxi Wu; Yuanjia Wang; Wenxue Xiao; Huamao Wei; Ru Jia; Tao Huang; Wenge Yang; Zhaohui Qiao (Food Chemistry, 2025)

Natural and built environments and heart failure risk: An exposome-wide analysis in the UK Biobank - Xuewei Huang; Siyu Yin; Meng Yao; Fang Lei; Weifang Liu; Lijin Lin; Tao Sun; Yuanyuan Cao; Xingyuan Zhang; Ru Li; Liwen Wang; Yufeng Hu; et al. (Environmental Research, 2025)

Selective energy transfer via chromium clusters for high-performance blue-excitable shortwave infrared phosphors - Shih-En Chen; Kuan-Chun Chen; Chuan-Fang Tsao; Yu-Chieh Huang; Agata Lazarowska; Mikołaj Kamiński; Natalia Majewska; Tadeusz Leśniewski; Grzegorz Leniec; Ewa Mijowska; Ding-Hwa Cherng; Ting-Wei Yeh; et al. (Chemical Engineering Journal, 2025)

Isorhamnetin alleviates acute liver injury by blocking ferroptosis - Didi Liu; Yao Zeng; Tao Meng; Yi Ru; Xinru Zhou; Yun Huang; Wei Jiang; Xueting Lang; Ye Tao; Yi Huang (Chemical Engineering Journal, 2025)

Correction: Combining network Pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Combining network pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

GZR101, a Novel Premixed Insulin for the Treatment of Diabetes Mellitus - Wei Chen; Cheng Cui; Wancai Xing; Yining Zhang; Anshun He; Yue Wang; Yan Huang; Nannan Zhai; Qimin Shi; Fangkai Xue; Yongchun Wang; Jun Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

GNF-5837 attenuates acute liver injury by inhibiting oxidative stress - Xinru Zhou; Xianyu Luo; Qian Huang; Yi Ru; Didi Liu; Maoyuan Linghu; Yi Huang (Molecular Biology Reports, 2025)

Renal Denervation Improves Myocardial Mitochondrial Dysfunction and Myocardial Fibrosis by Inhibiting the NE/KLF15/renalase Pathway - Ye Chen; Ru Fu; Miao Huang; Tao Liu; Lixiong Zeng; Xiaogang Li (Molecular Neurobiology, 2025)

Transcriptome analysis reveals no obvious unintended effects in the spleen of CRISPR/Cas9-mediated CD163 and pAPN double-knockout pigs - Zhi-Guo Liu; Nan Wang; Wan-Jie Wang; Lei Huang; Shun-Shun Chi; Yu-Xin Nie; Mao-Sha Yuan; Ya-Ru Sun; Yu-Lian Mu; Kui Li (Functional & Integrative Genomics, 2025)

Association between legume consumption and risk of esophageal cancer among Chinese adults: a 17-year prospective cohort study - Fengyi Huang; Xiaorui Zhang; Jiayue Li; Xinqing Li; Ru Chen; Shaoming Wang; Fen Liu; Wenqiang Wei (Cancer Causes & Control, 2025)

Trichoderma azadirachtae Ta3302: A novel biocontrol agent for banana Fusarium wilt and a promoter of plant growth - Mei Luo; Qiu-Rong Huang; Meng-Xuan Jia; Jin-Ying Zeng; En-Ru Dong; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2025)

Elucidating the impact of salt concentration on volatile flavor profiles and microbial dynamics in fermented cockle paste using GC-IMS and high-throughput 16S rDNA sequencing - Shi-meng Sun; Jia-bo Huang; Jing Li; Jing-ru Chen; Peng-fei Jiang (Food Research International, 2025)

Cross-altitude distribution patterns of bacterial communities in Chinese rivers: evidence from meta-analysis - Ru Liu; Peng Wang; Qinwei Chen; Wang Shu; Mingjun Ding; Minghua Nie; Gaoxiang Huang; Hua Zhang (Environmental Research, 2025)

Inhibition of the NLR pathway alleviates MAPK1 mutation-driven proliferation and differentiation deficits and enhanced apoptosis in P19 cells - Tingying Lei; Lei Liu; Fei Guo; Ru Li; Li Zhen; Fang Fu; Min Pan; Jin Han; Hang Zhou; Chunling Ma; Ruibin Huang; Xinyi Zhao; et al. (Tissue and Cell, 2025)

Salicylic acid promotes arsenic uptake in Pteris vittata via regulation of key genes and elevated nitric oxide and spermidine - Zhi-Hua Dai; Ze-Chao Li; Xi Chen; Ru Huang; Jian-Hua Sun; Chen-Jing Liu; Lena Q. Ma; Ru-Yi Yang (Journal of Hazardous Materials, 2025)

Protein structural transitions and cryo-stability of shrimp gel: Effects of setting time at 30 °C in a novel processing system - Kaina Duan; Lechang Sun; Jie-ting Geng; Wenge Yang; Huamao Wei; Tao Huang; Ru Jia (Innovative Food Science & Emerging Technologies, 2025)

Effect of ice crystal formation on the mechanical and protein properties of grass carp (Ctenopharyngodon idella) flesh: Contributions of salt ions and freezing rate - Yajin Zhang; Huiyuan Jin; Ziaur Rahman; Shanbai Xiong; Tao Yin; Ru Liu; Qilin Huang; Juan You (Food Chemistry, 2025)

The threat of microplastics to human kidney health: Mechanisms of nephrotoxicity and future research directions - Ru-Yu Tan; Qin-Ying She; Yun-Ci Ma; Ming-Hong Liu; Li-Juan Li; Li-Li Huang; Yi-Wen Zhong; Hui-Xin Bi (Environmental Research, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

Graft-modified amphiphilic dendron/polyimide regular through-pore composite membranes for oil/water separation - Chien-Chieh Hu; Cai-Syuan Sung; Ru-Jong Jeng; Chien-Hsin Wu; Ying-Chi Huang; Huai-Che Chang; Kueir-Rarn Lee; Juin-Yih Lai (Chemical Engineering Journal, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Bigels as novel fat substitutes: fat simulation characteristics, quality regulation, future trends and challenges - Yanlei Gao; Qing Xiong; Qilin Huang; Yang Hu; Ru Liu (Trends in Food Science & Technology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

FlexiSAM: A flexible SAM-based semantic segmentation model for land cover classification using high-resolution multimodal remote sensing imagery - Zhan Zhang; Daoyu Shu; Cunyi Liao; Chengzhi Liu; Yuanxin Zhao; Ru Wang; Xiao Huang; Mi Zhang; Jianya Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Waste to wealth: High-internal phase Pickering emulsions stabilized by defatted flaxseed particles were employed as a novel animal fat replacer in meat systems - Cheng-wei Ruan; Si-ying Huang; Jun-ru Qi; Qingrong Huang (Food Chemistry, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Human-mediated introductions mitigate climate vulnerability of mangrove species by releasing their ecological potential - Wen-Xun Lu; Wen-Qin Tu; Bing-Huang Zhang; An-Ru Lou; Sheng-Chang Yang (Biological Conservation, 2025)

Endothelial Cell Integrin α6 Regulates Vascular Remodeling Through the PI3K/Akt-eNOS-VEGFA Axis After Stroke - Bing-Qiao Wang; Yang-Ying Duan; Mao Chen; Yu-Fan Ma; Ru Chen; Cheng Huang; Fei Gao; Rui Xu; Chun-Mei Duan (Neuroscience Bulletin, 2025)

Carnosic Acid Attenuated the Motor Impairment by Bisphenol A is Related to the Regulation of Autophagy Through Parkin in In Vitro and In Vivo - Chun-Huei Liao; Ya-Chen Shih; Hsi-Yun Huang; Jing-Wei Chen; Shao-I Hsu; Chiao-Ni Lai; Ru-Huei Fu; Chia-Wen Tsai (Molecular Neurobiology, 2025)

Architectural features and antioxidative biofunctionality of a novel pectin from Angelica keiskei Koidz - Si-Ru Chen; Yu-Ru Zhu; Li-Ting He; Hong-Liang Sun; Jing Huang; Yan-Zi Yang; Hua-Jun Zhao; Bo Yang; Meng-Xia Yan (Natural Product Research, 2025)

Avian reovirus induces autophagy-mediated cargo of progeny viruses to extracellular vesicles and enhancement of virus release - Chao-Yu Hsu; Wei-Ru Huang; I.-Hsun Chiang; Jyun-Yi Li; Muhammad Munir; Hung-Jen Liu (Veterinary Microbiology, 2025)

Oncolytic avian reovirus regulates the TLR3-IRF3-IFN-γ-JAK-STAT1 and TLR3-NF-κB-IFN-γ-JAK-STAT1 pathways inducing autophagy in murine melanoma cells - Chao-Yu Hsu; Zi-Yang Lo; Yi-Ying Wu; Wei-Ru Huang; Tz-Chuen Ju; Kuo-Pin Chuang; Lon-Fye Lye; Muhammad Munir; Hung-Jen Liu (Veterinary Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

Factors affecting seed germination in critically endangered Salvia daiguii: Seed quality, temperature and light, osmotic potential, pH, hand pollination, hormones, and mucilage - Han-Wen Xiao; Ruo-Qing Jiang; Yan-Bo Huang; Ru-Nan Tian (Journal for Nature Conservation, 2025)

Thermophilic degradation of sulfamethazine by Geobacillus sp. S-07: pathway and mechanism - Ting Pan; Yan-Yan Zhou; Xu Huang; Jian-Xin Xu; Xiao-Yu Guo; Jian-Qiang Su; Hu Li; Xiao-Ru Yang (Environmental Research, 2025)

Association between domestic cat hepadnavirus and feline hepatocellular carcinoma - M. Chun Chen; J. Pedro Cavasin; Y. Ru Choi; J. Michael Cullen; M.J. Dobromylsky; W. Huang; Y. Huang; P.A. Pesavento; J.A. Lidbury; J.M. Steiner; J.A. Beatty (Journal of Comparative Pathology, 2025)

Comprehensive molecular biology and metabolomics analysis reveal the changes on muscle quality of Megalobrama amblycephala exposure to ammonia nitrogen during transportation - Ling Peng; Ziaur Rahman; Yuanyong Tian; Tao Yin; Shanbai Xiong; Juan You; Ru Liu; Lan Wang; Qilin Huang; Huawei Ma (Food Research International, 2025)

Schiff base crosslinking based dialdehyde-chitosan/gelatin/tea polyphenol electrospun nanofibrous membranes with excellent antibacterial and antioxidant activity for food packaging - Yu Ma; Ru Tian; Yudong Song; Mengxiao Liu; Jie Li; Zhichun Bi; Hui Huang; Yongxin Li (Food Packaging and Shelf Life, 2025)

Safranal ameliorates atherosclerosis progression partly via repressing PI3K/Akt and NF-κB signaling pathways in ApoE (−/−) mice - Yining Geng; Manping Song; Bing Huang; Ru Lin; Shiwen Wu; An Lin (Journal of Natural Medicines, 2025)

Gelatin based preservation technologies on the quality of food: a comprehensive review - Qingfang Ying; Shengnan Zhan; Haixia Yu; Jihua Li; Ru Jia; Huamao Wei; Eugeni Roura; Xinle Tan; Zhaohui Qiao; Tao Huang (Critical Reviews in Food Science and Nutrition, 2025)

Enhancement mechanism of residue Gd (III)-induced in anaerobic ammonia oxidation for nitrogen removal from rare earth tailings leachate - Xiangyi Deng; Ting Zeng; Shengnan Huang; Chunqiao Xiao; Liu Liu; Wanqiang Dong; Zhenyue Zhang; Ru’an Chi (Journal of Environmental Chemical Engineering, 2025)

Efflux pumps of Pseudomonas aeruginosa and their regulatory mechanisms underlying multidrug resistance - Wen-Ru Li; Zhi-Qing Zhang; Kang Liao; Qing-Shan Shi; Xu-Bin Huang; Xiao-Bao Xie (International Biodeterioration & Biodegradation, 2025)

Fabrication, characterization, and application in 3D printing of high internal phase emulsion stabilized by alkaline thermal treated pea protein and pectin complex - Ru Zhao; Boxue Xia; Abbas Khan; Yanjiao Chang; Xin Guo; Yaxuan Liu; Xin Huang; Cuina Wang (Food Research International, 2025)

Effects of modified KGM on the gelling capability of fish protein: Novel insights into hooking effect - Ziaur Rahman; Sijin Zhang; Arsalan Khan; Juan You; Ru Liu; Qilin Huang; Huawei Ma; Soottawat Benjakul; Tao Yin (Food Chemistry, 2025)

Differential analysis of microorganisms and flavor substances during drying of scallops (Chlamys farreri) based on high-throughput sequencing and headspace gas chromatography-mass spectrometry (HS-GC-MS) - Jing-ru Chen; Jia-bo Huang; Shi-meng Sun; Peng-fei Jiang (Food Bioscience, 2025)

Combined exposure to atrazine and phoxim exacerbated the alterations of enzyme activity and abnormal gene expression in earthworms (Eisenia fetida) - Jinzhan Li; Jingwen Wang; Fang Shu; Nan Huang; Ru Jia; Yanhua Wang (Environmental Toxicology and Pharmacology, 2025)

Superior ammonia nitrogen adsorption capacity and reusability biochar microsphere applied in live fish transportation - Ling Peng; Tao Yin; Zhiyong Song; Shanbai Xiong; Ru Liu; Juan You; Qiling Huang (Chemical Engineering Journal, 2025)

Strategic carbon source supplementation enhances nitrite degradation by Pantoea sp. A5 in variable temperature conditions - Tzu-Yuan Sung; Anil Kumar Patel; Shang-Ru Lin; Chuan-Ting Huang; Ying-Tang Huang (Bioresource Technology, 2025)

Asymbiotic Nitrogen Fixation in the Phyllosphere of Urban Green Spaces - Jian-Feng Li; Le-Yang Yang; Zhao Zhang; Xin-Rong Huang; Hu Li; Shun Li; Xiao-Ru Yang (Current Microbiology, 2025)

Intensive rotational grazing has positive effects on productivity of rangeland - Ping Ge; Jianguo Xue; Yaqian Ru; Yulin Li; Dongxu Li; Peng Han; Ang Li; Jianhui Huang (Agriculture, Ecosystems & Environment, 2025)

A late summer temperature reconstruction based on tree-ring maximum latewood density since AD 1246 on the southeastern Tibetan Plateau - Ru Huang; Hong Yin; Haifeng Zhu; Eryuan Liang; Atta Ullah; Wolfgang Jens-Henrik Meier; Fayaz Asad; Achim Bräuning; Jussi Grießinger (Quaternary Science Reviews, 2025)

Air pollution and corporate innovation under China’ s new and stringent round of environmental regulations - Xinying Huang; Ru Chen; Ying Kong; Ruoyan Zhang (Journal of Environmental Management, 2025)

Collagenases from hepatopancreas and muscle of Litopenaeus vannamei: Purification, characterization and comparison of their behaviors in collagen degradation - Xu-Chen Xiao; Jia-Yin Huang; Yu-Lei Chen; Kai-Yuan Cao; Ru-Qing Yang; Duan-Quan Lin; Shu-Jun Hong; Yu-Ting Yang; Min-Jie Cao (Food Chemistry, 2025)

Changes in physicochemical properties of snakehead fish slices incorporated with nano fish bones during freeze-thaw cycles: Effects of marinating methods - Ziaur Rahman; Yajin Zhang; Abroo Tabasum; Jirawat Yongsawatdigul; Qilin Huang; Shanbai Xiong; Juan You; Ru Liu; Tao Yin (Food Chemistry, 2025)

Electrospun nanofiber membranes based on dialdehyde pullulan polysaccharide and schiff base crosslinked lysozyme for antibacterial packaging of blueberries - Yu Ma; Ru Tian; Yudong Song; Chenghui Yin; Hui Huang; Yongxin Li (Food Bioscience, 2025)

Chlorinated paraffins exposure in particulate matter increase the risk of attention-deficit/hyperactivity disorder symptoms in children and adolescents - Wan-Ting He; Jing-Wen Huang; Yun-Ting Zhang; Edwin Trevathan; Zhengmin Qian; Ri'enna Boyd; Michael Elliott; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Guang-Hui Dong (Environmental Pollution, 2025)

Spatially confined Co nanoparticles in N doped carbon material for high efficiency capacitive deionization - Jianwei Wu; Yuzudi Tong; Xinhua Huang; Dongyin Qin; Ruikun Zhao; Ru Li; Guangzhi Hu (Desalination, 2025)

Enhancing color conversion of perovskite quantum dot-based micro-light-emitting diodes via electrochemical etching and flow chemistry system - Wen-Tse Huang; Yen-Huei Lin; Po-Yi Tu; Loan Thi Ngo; Wei-Cheng Chen; Kai-Ling Liang; Yen-Hsiang Fang; Chaochin Su; Ru-Shi Liu (Chemical Engineering Journal, 2025)

Targeted restoration of endothelial hypoxic response prevents angiogenic bone loss against liver fibrosis - Nan Zhang; Sheng-Feng Bai; Jia-Ning Liu; Xin Huang; Lu Liu; Yu-Ru Gao; Si-Qi Ying; Chen-Xi Zheng; Hao-Kun Xu; Ji Chen; Xiao Lei; Yu-Bo-Han Zhang; et al. (Chemical Engineering Journal, 2025)

Metagenomics and metatranscriptomics uncover the regulatory mechanism of nitrogen metabolism response to aggregation status of anammox bacteria - Ru Wang; Jinshi Lian; Wenyan Wang; James P. Shapleigh; Longxing Jiang; Yahui Wang; Yan Huang; Ling Xie; Liangwei Deng; Wenguo Wang; Lan Wang (Chemical Engineering Journal, 2025)

Corrigendum: Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2025)

First report of Botryosphaeria wangensis, Colletotrichum nymphaeae, Diaporthe eres, and Geotrichum candidum causing postharvest fruit rot of plums (Prunus salicina) in China - Yu-Ru Wang; Bo-Ying Huang; Hafiz Muhammad Usman; Khadija Javed; Fatimah Al-Otibi; Kevin D. Hyde; Yong Wang (Crop Protection, 2025)

Quantitational life cycle assessment of Effluent-Energy-Carbon synergies and trade-offs in drinking water treatment plant upgrades - Yumeng Zhang; Zongqi Ding; Zewei Lin; Shoubin Chen; Shunjian Cheng; Kaiming Peng; Ru Guo; Xiangfeng Huang; Chen Cai; Jia Liu (Journal of Water Process Engineering, 2025)

Enhanced effects and mechanisms of Tween80 on aniline biodegradation by newly isolated Pseudomonas veronii T1 - Yufeng Fu; Tingdi Zhang; Chuanyu Qin; Chengwu Zhang; Jintao Ru; Rui Tang; Guoxin Huang; Jian Chen (Journal of Environmental Chemical Engineering, 2025)

Granitoid genesis and related rare metal mineralization of the Shihuiyao Rb–Ta–Nb deposit in the Southern Great Xing’an Range, NE China - Shi-Heng Bai; Yu Huang; Zhi-Jie Feng; Matthew J. Brzozowski; Yao-Hui Jiang; Ru-Xiong Lei; Chang-Zhi Wu (Gondwana Research, 2025)

Preparation of two-step cold-set low oleogel-microgels phase bigels and its application in tender fish balls: Pork fat substitute and cryoprotectant - Yanlei Gao; Qing Xiong; Qilin Huang; Yang Hu; Ru Liu (Food Research International, 2025)

Granular ferric hydroxide adsorption as a pretreatment to achieve phosphorus reclamation and high water-recovery wastewater effluent desalination - Hao Huang; Ru Liu; Mangut Sunday Jikmyan; Shihong Lin; Oded Nir; Roy Bernstein (Chemical Engineering Journal, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

Leveraging Deep Learning to Extract Raindrop Size Gamma Distribution Parameters from Wind Profile Radar Data - Yu Huang; Zhiqun Hu; Lin Li; Ru Zhou; Xu Lu; Mengyu Huang (Journal of Meteorological Research, 2025)

Location optimization of unmanned aerial vehicle (UAV) drone port for coastal zone management: The case of Guangdong coastal zone in China - Jia Sun; Sijing Shu; Hongda Hu; Yingbin Deng; Zhao Li; Shengnan Zhou; Yue Liu; Minwen Dang; Wumeng Huang; Zhiwei Hou; Xiaoling Yin; Ru Zhang; et al. (Ocean & Coastal Management, 2025)

Seasonal variation of diurnal rainfall characteristics over Vietnam - Wan-Ru Huang; Hai Bui-Manh; Tzu-Yang Chiang; Suranjith Bandara Koralegedara (Science of The Total Environment, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Study of the brittleness properties of granites under thermal and mechanical action through a new brittleness evaluation method - Huijun Lu; Ru Zhang; Li Ren; Anlin Zhang; Zidong Fan; Kun Xiao; Wei Liu; Tao Huang (Geothermics, 2025)

Mechanism of enhanced quality of Acetes chinensis powder-Alaska Pollock surimi: Gel properties, rheological properties, micro-structure - Qianqian Li; Jiehui Feng; Ru Jia; Huamao Wei; Tao Huang; Jinjie Zhang; Dalun Xu; Wenge Yang; Gaoshang Li (Food Research International, 2025)

Effect of cinnamaldehyde and tannic acid nano-emulsions on meat quality and protein oxidation during cold storage - Ramy M. Khoder; Xinqun Deng; Liangzi Zhang; Qilin Huang; Juan You; Ru Liu; Huawei Ma; Tao Yin (Food Packaging and Shelf Life, 2025)

Is there an association between eye-level greenness and childhood hypertension using street view? Findings from the Seven Northeastern Cities study in China - Huang-Min Yang; Jing-Yao Wang; Cheng Li; Ya-Qin Zhang; Ruoyu Wang; Qi Yang; Yao Yao; Zilong Wang; Shu-Li Xu; He-Hai Huang; Qian-Sheng Hu; Ru-Qing Liu; et al. (Environmental Research, 2025)

Drug–drug interaction of phenytoin sodium and methylprednisolone on voriconazole: a population pharmacokinetic model in children with thalassemia undergoing allogeneic hematopoietic stem cell transplantation - Yun Wu; Lu-lu Niu; Ya-yun Ling; Si-ru Zhou; Tian-min Huang; Jian-ying Qi; Dong-ni Wu; Rong-da Cai; Ting-qing Wu; Yang Xiao; Taotao Liu (European Journal of Clinical Pharmacology, 2025)

Glycosylation on the Antifreeze and Antioxidant Capacities of Tilapia Gelatin Hydrolysates - Ying Liu; Zongcai Tu; Qiuyu Lu; Shengnan Zhan; Ru Jia; Zhaohui Qiao; Huamao Wei; Tao Huang (Fishes, 2025)
The antifreeze and antioxidant capacities of tilapia (Oreochromis mossambicus) gelatin hydrolysates were investigated, after glycosylation with saccharides of varying molecular weights, to enhance their functional properties to widen its commercial application in frozen aquatic products. Glycosylation was conducted by mixing gelatin hydrolysates with ribose, glucose, maltose, and dextran (20 kDa) at a 1:1 mass ratio; the glycosylation products had a pH of 10 and were incubated at 80 °C for 1 h. The results showed that the glycosylation degree ranked as: ribose > glucose > maltose > dextran. The mass spectrometry analysis showed that 17, 32, and 5 glycosylation sites were identified for ribose, glucose, and maltose, respectively, suggesting a molecular weight-dependent effect. Spectroscopic analyses, including ultraviolet and infrared spectroscopy, revealed that the gelatin hydrolysate structure was expanded, with chromophores in hydrophilic environments; a blue shift in the amide A and II bands confirmed that the amino group was involved. Fluorescence spectroscopy showed conformational changes with a red shift at 303.4 nm and a reduction in intensity. Antifreeze activity, such as catalase freezing protection and shrimp surimi protein stability, and antioxidant activity, including radical scavenging and metal ion chelation, were significantly improved. Ribose exhibited the strongest effects, followed by maltose and glucose. These results demonstrate the potential of glycosylation to improve gelatin hydrolysates for functional applications.

Microplastic pollution in stony coral skeletons and tissues: A case study of accumulation and interrelationship in South Penghu Marine National Park, Taiwan Strait - Chih-Feng Chen; Yun-Ru Ju; Ming-Huang Wang; Yee Cheng Lim; Chiu-Wen Chen; Yu-Rong Cheng; Cheng-Di Dong (Journal of Hazardous Materials, 2025)

Insight into the mechanism of setting temperature and time on gel properties of Solenocera crassicornis surimi - Jiafang Lu; Jingjing Tong; Dalun Xu; Huamao Wei; Tao Huang; Wenge Yang; Ru Jia (Food Research International, 2025)

Nano fish bone prepared by high-energy media milling extends the shelf life of tofu during cold storage: Unlocking the restriction on water mobility - Ramy M. Khoder; Liangzi Zhang; Qilin Huang; Juan You; Huawei Ma; Tao Yin; Ru Liu (Food Chemistry, 2025)

Polysaccharide modified fish gelatin intelligent hydrogels for reliable monitoring freshness of shrimp (Litopenaeus vannamei) - Qingfang Ying; Shengnan Zhan; Qiuyu Lu; Wenge Yang; Ru Jia; Gaoshang Li; Tao Huang (Food Hydrocolloids, 2025)

Data imbalance causes underestimation of high ozone pollution in machine learning models: A weighted support vector regression solution - Ling Zhen; Baihua Chen; Lin Wang; Lin Yang; Wei Xu; Ru-Jin Huang (Atmospheric Environment, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Carboxymethyl chitosan-assisted formation of stable soy protein isolate emulsions and their impact on the properties of squid (Dosidicus gigas) surimi gel - Siqi Liu; Zhufen Wang; Wenge Yang; Tao Huang; Jie-Ting Geng; Huamao Wei; Yuanpei Gao; Ru Jia (Food Hydrocolloids, 2025)

Leveraging Bio-Waste onion skin for High-Performance triboelectric nanogenerators - Po-Yen Chang; Ting-Ying Huang; Chien-Hung Yang; Chia-Hsien Lee; Ru-Jong Jeng; Chih-Ping Chen; Meng-Fang Lin (Chemical Engineering Journal, 2025)

Enhancing capacitive desalination efficiency via atomically dispersed Fe in N/P doped carbon material - Zhirou Wang; Xinhua Huang; Yuzudi Tong; Tong Wang; Mai Xu; Ru Li; Guangzhi Hu (Chemical Engineering Journal, 2025)

Automatic and integrated detection of nucleic acid by using a dual-mode thermal controlled digital microfluidic chip - Jiaqi Liao; Chonghao Li; Jiajia Liu; Hao Cheng; Linmin Li; Guixi Tang; Ru Huang; Yating Lu; Siyue Chen; Qian Zhang; Hao Chen; Qinyuan Chen; et al. (Analytica Chimica Acta, 2025)

Heavy metal emissions from on-road vehicles in Xia-Zhang-Quan metropolitan area in southeastern China from 2015 to 2060: impact of vehicle electrification - Zhe-Nan Wen; Qi-Yu Miao; Jiang-Ru Chen; Shui-Ping Wu; Li-Xiong He; Bing-Qi Jiang; Yi-Jing Liu; Zhi Huang (Environmental Science and Pollution Research, 2024)

Design and experimental analysis of real-time detection system for The seeding accuracy of rice pneumatic seed metering device based on the improved YOLOv5n - He Xing; Yikai Wan; Peng Zhong; Junjiang Lin; Mingtao Huang; Ru Yang; Ying Zang (Computers and Electronics in Agriculture, 2024)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Enhancing natural carbon sinks: Simulation of land use change under different carbon market scenarios by developing an ANN-ABM model - Ruimin Lin; Ru Guo; Yunyang Li; Guanghui Shao; Yuhao Zhang; Kaiming Peng; Xiangfeng Huang (Resources, Conservation and Recycling, 2024)

Estimating monthly NO2, O3, and SO2 concentrations via an ensemble three-stage procedure with downscaled satellite remote sensing data and ground measurements - Chu-Chih Chen; Yin-Ru Wang; Fu-Cheng Wang; Yi-Shiang Shiu; Chang-Fu Wu; Tang-Huang Lin (Journal of Hazardous Materials, 2024)

A novel hybrid variable cross layer-based machine learning model improves the accuracy and interpretation of energy intensity prediction of wastewater treatment plant - Yucheng Li; Chen Cai; Erwu Liu; Xiaofeng Lin; Ying Zhang; Hongjing Chen; Zhongqing Wei; Xiangfeng Huang; Ru Guo; Kaiming Peng; Jia Liu (Journal of Environmental Management, 2024)

Developing novel microwave-assisted induction heating (MAIH) technology for heating in-packaged ready-to-eat chicken breast products - Chiu-Chu Hwang; Yu-Ru Huang; Cheng-Da Hsieh; Yi-Chen Lee (Innovative Food Science & Emerging Technologies, 2024)

Ovalbumin/sodium alginate Pickering emulsion: Structural characteristics and its contribution to enhancing the gel properties of Hairtail (Trichiurus haumela) surimi - Zhufen Wang; Siqi Liu; Wenge Yang; Jie-Ting Geng; Tao Huang; Huamao Wei; Zhaohui Qiao; Ru Jia (Food Chemistry, 2024)

The impact of the addition of vitamin C, NaCl, clove oil on the muscle of live blunt-snout bream during transportation - Yu Chen; Ramy M. Khoder; Jun Mei; Hong Yang; Qilin Huang; Juan You; Tao Yin; Ru Liu (Food Bioscience, 2024)

A loss-of-function mutation in OsTZF5 confers sensitivity to low temperature and effects the growth and development in rice - Limin Wang; Ru Wang; Xin Cai; Huiqi Zheng; Yuxing Huang; Yuechen Li; Mingyue Cui; Mingli Lin; Huiwu Tang (Plant Molecular Biology, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Effect of Sodium Alginate and Calcium Chloride on the Physicochemical Characteristics of Shrimp (Penaeus Vannamei) Surimi Gels - Ziyan Wang; Jiehui Feng; Qianqian Li; Ru Jia; Tao Huang; Huamao Wei; Wenge Yang (Journal of Ocean University of China, 2024)

Emergency control of dinoflagellate bloom in freshwater with chlorine enhanced by solar radiation: Efficiency and mechanism - Ru Wang; Ya Cheng; Qiqi Wan; Ruihua Cao; Jie Cai; Tinglin Huang; Gang Wen (Water Research, 2024)

Revisiting the impact of temperature on ground-level ozone: A causal inference approach - Baihua Chen; Ling Zhen; Lin Wang; Haobin Zhong; Chunshui Lin; Lin Yang; Wei Xu; Ru-Jin Huang (Science of The Total Environment, 2024)

Single-step synthesis of NiS2 based on deep eutectic solvent: Mechanistic insights and adsorption performance for rhodamine B - Yuan Zhang; Juanjian Ru; Ping Huang; Enhui Wu (Journal of Water Process Engineering, 2024)

Proteomic analysis revealed the deterioration of surimi gelling capability to fish stress during transportation - Zhiying Xiang; Tao Yin; Zenan Huang; Ziaur Rahman; Yongsawatdigul Jirawat; Tanye Xu; Qilin Huang; Juan You; Ru Liu; Hong Yang (Food Research International, 2024)

Impacts of food additives on gut microbiota and host health - Ping Li; Ru Qu; Ming Li; Ping Sheng; Liang Jin; Xiaochang Huang; Zhenjiang Zech Xu (Food Research International, 2024)

ESR chronology of the Quaternary sedimentary sequence of the Shinaimiao borehole in Hebi City, Henan Province, China - Hao Ji; Zhong-shan Shen; Chun-Ru Liu; Xiong-Nan Huang; Xiao-Ping Yang; Chuan-Yi Wei; Xin-Xiu Li; Qing Zhou; Gong-Ming Yin (Quaternary Geochronology, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Metabolic pathways altered by air pollutant exposure in association with coagulation function among the rural elderly - Haoyu Huang; Ru-Qing Liu; Yan Chen; Yuewei Liu; Guang-Hui Dong; Jian Hou; Shanshan Li; Yuming Guo; Chongjian Wang; Gongbo Chen (Journal of Hazardous Materials, 2024)

Technology-driven carbon-neutral pathway analysis for Urban Wastewater Treatment Plants - Haoran Wu; Chen Cai; Lian Yu; Zhenxing Shang; Yumeng Zhang; Xiaojing Ni; Ru Guo; Jia Liu; Kaiming Peng; Xiangfeng Huang; Limin Zhang; Zhaochang Huang; et al. (Journal of Cleaner Production, 2024)

Insight into the mechanism on nano fish bone improving the quality of marinated snakehead fish slices during freeze-thaw cycles - Ziaur Rahman; Tao Yin; Ramy M. Khoder; Abroo Tabasum; Qilin Huang; Juan You; Huawei Ma; Ru Liu; Shanbai Xiong (Innovative Food Science & Emerging Technologies, 2024)

Plantago asiatica seed as a protective agent for mitigating metals toxicity on Penaeus vannamei - Zhen-Hao Liao; Yeh-Fang Hu; Wen-Shao Wu; Huu-The Nguyen; Sofia Priyadarsani Das; Huai-Ting Huang; Yu-Ru Lin; Po-Tsang Lee; Fan-Hua Nan (Fish & Shellfish Immunology, 2024)

Bi2O3/Bi@CSs achieved by shock-type heating for fast and long-lasting sodium ion battery - Ya Ru Pei; Xue Jing Yang; Wu Bin Wan; Hai Ming Huang; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2024)

Combined effects of nitrogen limitation and overexpression of malic enzyme gene on lipid accumulation in Dunaliella parva - Shi-Yu Liang; Li-Hua Li; Meng-Xiang Ling; Lei Mo; Li-Mei Huang; Ling-Ru Ruan; Chang-Hua Shang (Bioresource Technology, 2024)

HER2 mutations in advanced cervical neuroendocrine carcinoma: implications for trastuzumab deruxtecan therapy - Wan-Ru Chao; Ming-Yung Lee; Gwo-Tarng Sheu; Yi-Ju Lee; Huang-Pin Shen; Chih-Ping Han (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Bacterial functions are main driving factors on paddy soil organic carbon in both surface soil and subsoil - Xiang-Wen Huang; Jia-Jun Lin; De-Jin Li; Xiang-Qi Huang; Qi-Huan Xie; Sheng-Gang Pan; Xiang-Ru Tang; Jian-Ying Qi (Agriculture, Ecosystems & Environment, 2024)

Effects of melatonin on sperm quality, enzyme activity, antioxidant gene expression and fertility of cryopreserved bovine semen - Peng Niu; Fei Huang; Jie Wang; Jia-jia Suo; Jie-ru Wang; Di Fang; Chun-mei Han; Qing-hua Gao (Theriogenology, 2024)

Upgrading the industrial structure for optimizing water-energy-carbon nexus in regional trade network - Benshuo Zhu; Ru Guo; Yun-en Tang; Kaiming Peng; Xiangfeng Huang (Journal of Cleaner Production, 2024)

Enhancing vitamin D3 bioaccessibility: Unveiling hydrophobic interactions in soybean protein isolate and vitamin D3 binding via an infant in vitro digestion model - Jia-Rong Huang; Jing-Ru Song; Wan-Shuang Cai; Zhen-Wen Shao; Da-Yong Zhou; Liang Song (Food Chemistry, 2024)

Supramolecular assembly of dual crosslinked nanocomposite polysaccharides hydrogel: Integration of injectable, self-healing, and pH-responsive platform for sustained delivery of polyphenols - Fatima-ezzahra Ettoumi; Hao Huang; Yanqun Xu; Lei Wang; Qiaomei Ru; Yichen Hu; Liang Zou; Zisheng Luo (Food Hydrocolloids, 2024)

Alginate/silk fibroin/Zn2+ composite microspheres for site-specific delivery for enhanced ulcerative colitis therapy - Yaoyao Du; Yuting Jiang; Yijie Song; Jie Chen; Yueqian Wu; Ru Guo; Yihao He; Lan Shen; Bing Wang; Shaogang Huang; Yongzhuo Huang (Chemical Engineering Journal, 2024)

Biofunctionalized hydrogel composed of genipin-crosslinked gelatin/hyaluronic acid incorporated with lyophilized platelet-rich fibrin for segmental bone defect repair - Er-Yuan Chuang; Yi-Cheng Lin; Yu-Min Huang; Chih-Hwa Chen; Yi-Yen Yeh; Lekha Rethi; Yu-Jen Chou; Pei-Ru Jheng; Jen-Ming Lai; Chang-Jung Chiang; Chin-Chean Wong (Carbohydrate Polymers, 2024)

Effects of Taiwanese indigenous cinnamon (Cinnamomum osmophloeum) leaf hot-water extract on nonspecific immune responses, resistance against Vibrio parahaemolyticus, nonviable cells, and haemocyte subpopulations in white shrimp (Penaeus vannamei) - Muhammad Ar Rozzaaq Nugraha; Yu-Ru Lin; Novi Rosmala Dewi; Huai-Ting Huang; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2024)

Enhancing open-circuit voltage and suppression of energy loss in ternary organic photovoltaics utilizing carbazole/bicarbazole-based guest donors - Chun-Yu Lin; Bing-Huang Jiang; Pei-Jui Weng; Yu Hsuan Lin; Yu-Wei Su; Hui-Shan Shih; Zhong-En Shi; Yan-Ru Lin; Jijitha Vailassery; Shih-Sheng Sun; Chih-Ping Chen; Yuan Jay Chang (Chemical Engineering Journal, 2024)

Tree-ring based summer temperature variability since 1790 CE in the Hindu Kush region of northern Pakistan - Fayaz Asad; Muhammad Adil; Sabrina Shahid; Nasrullah Khan; Ru Huang; Haifeng Zhu (International Journal of Biometeorology, 2024)

Numerical modeling on wave–current flows and bed shear stresses over an algal reef - Yi-Ru Lan; Zhi-Cheng Huang (Environmental Fluid Mechanics, 2024)
Currents in coastal zones under multiple mechanisms in terms of tides, waves, wind, and high roughness are difficult to model; bed shear stresses under wave–current flows are particularly challenging yet not being well studied. Few studies reported the modeling and validation of the bed shear stress in reef environments. In this paper, we present the first direct assessment of numerical modeling on depth-averaged currents and bed shear stresses over an algal reef using a coupled wave–current model (Delft-3D). The modeled results were validated and compared to the field observed data. The model considers hydrodynamic forcing in terms of tides, waves, wind stresses, and bed friction. Results show that the model generally reproduces the depth-averaged currents and bed shear stresses when considering all the mechanisms. Two numerical cases with and without wind forcing were tested to examine the effects of the winds. We found that the tide is mostly the primary factor driving the current, even in shallow waters within a depth of 3 m; however, the currents are also significantly affected by wind speeds and wind directions during high-wind events. When the wind direction is in the same direction as the tidal current, the current speed increases, suggesting the importance of the wind stress on the coastal currents. In addition, two models were chosen to study the nonlinear enhancement of bed shear stress by waves. We found a significant difference between the two models in predicting the bed shear stresses compared to the observed data. Nonlinear contribution from wave enhances the magnitude of bed shear stresses, which reduces the model error. The results highlight the nonlinear interaction between waves and currents is meaningful in predicting the bed shear stresses during high-wave-orbital motions; improvement of the present wave-current nonlinear interaction model for predicting the bed shear stresses may be needed.

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Asperidulins A and B, two new prenylxanthone derivatives from an apple-derived fungus Aspergillus nidulans KIB-HACM-01 - Peng Lai; Li Wang; Chenjie Deng; Yixin Xu; Xiao-Yan Ma; Chun-Ru Cheng; Sheng-Xiong Huang (Natural Product Research, 2024)

Effects of different phosphorylation times and pH on fish gelatin: Functional properties, structural and mechanism analysis - Bin Hu; Shijie Cen; Wanyi Sun; Shengnan Zhan; Ru Jia; Changrong Ou; Tao Huang (Food Hydrocolloids, 2024)

Carbon-in-carbon: Hybrid carbonized nanomaterials with multifunctional activities for the treatment of endophthalmitis - Hong-Jyuan Jian; Yi-Ru Chiou; Anisha Anand; Chien-Fu Chen; David Hui-Kang Ma; Jui-Yang Lai; Chih-Ching Huang; Huan-Tsung Chang (Chemical Engineering Journal, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Sex-inclined microRNAs in serum exosomes for sex determination in the greater amberjack (Seriola dumerili) - Qiuxia Deng; Yang Huang; Can Zhao; Xiaoying Ru; Ruijuan Hao; Na Zhao; Bo Zhang; Chunhua Zhu (Aquaculture, 2024)

Poleward migration of tropical corals inhibited by future trends of seawater temperature and calcium carbonate (CaCO3) saturation - Ya-Yi Huang; Ting-Ru Chen; Kim Phuong Lai; Chao-Yang Kuo; Ming-Jay Ho; Hernyi Justin Hsieh; Yi-Chia Hsin; Chaolun A. Chen (Science of The Total Environment, 2024)

CIP1, a CIPK23-interacting transporter, is implicated in Cd tolerance and phytoremediation - Jiayi Wang; Huihui Zhu; Ru’nan Huang; Jiming Xu; Li Huang; Jianli Yang; Weiwei Chen (Journal of Hazardous Materials, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Application of a water-energy-carbon coupling index to evaluate the long-term operational stability of the anaerobic-anoxic-oxic-membrane bioreactor (A2/O-MBR) process under the influence of rainstorms - Lian Yu; Kaiming Peng; Yizhen Huang; Feng Chen; Shoubin Chen; Yulong Xia; Xiangfeng Huang; Xiaojing Ni; Ru Guo; Chen Cai; Jia Liu (Water Research, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Direct and indirect monitoring methods for nitrous oxide emissions in full-scale wastewater treatment plants: A critical review - Zhenxin Shang; Chen Cai; Yanli Guo; Xiangfeng Huang; Kaiming Peng; Ru Guo; Zhongqing Wei; Chenyuan Wu; Shunjian Cheng; Youxiang Liao; Chih-Yu Hung; Jia Liu (Journal of Environmental Management, 2024)

Glycosylation with different saccharides on the gelling, rheological and structural properties of fish gelatin - Hulin Geng; Wanyi Sun; Shengnan Zhan; Ru Jia; Qiaoming Lou; Tao Huang (Food Hydrocolloids, 2024)

Redirecting surface reconstruction of CoP-Cu heterojunction to promote ammonia synthesis at industrial-level current density - Li Gan; Xiaoxue Zhang; Lei Guo; Muhammad Ajmal; Ru Jia; Xiaolei Guo; Chengxiang Shi; Lun Pan; Faryal Idrees; Xiangwen Zhang; Zhen-Feng Huang; Guidong Yang; et al. (Chemical Engineering Journal, 2024)

Opportunist ant species dominate metropolitan microhabitats: Evidence from the eastern margin of the Qinghai-Tibetan plateau - Ru-Yi Yin; Xin-Yu Luo; Xiang-Qin Huang; Zi-Xuan Zhao; Chris Newman; Yi Luo; Zhao-Min Zhou (Soil Biology and Biochemistry, 2024)

Sources-attributed contributions to health risks associated with PM2.5-bound polycyclic aromatic hydrocarbons during the warm and cold seasons in an urban area of Eastern Asia - Yu-Chieh Ting; Yu-Xuan Zou; Shih-Yu Pan; Yi-Ru Ko; Zih-Jhe Ciou; Chuan-Hsiu Huang (Science of The Total Environment, 2024)

Carbon emissions of urban rail transit in Chinese cities: A comprehensive analysis - Jing Pu; Chen Cai; Ru Guo; Jiangchuan Su; Ruimin Lin; Jia Liu; Kaiming Peng; Chaoguang Huang; Xiangfeng Huang (Science of The Total Environment, 2024)

Phosphonates-enhanced production of reactive oxygen species by ferrous ion in the presence of oxygen: Effects and mechanisms - Deyu Wang; Chengwu Zhang; Yingqi Wang; Hui Zhang; Jintao Ru; Chuanyu Qin; Guoxin Huang; Jian Chen (Journal of Environmental Chemical Engineering, 2024)

Construction of self-assembled nano cellulose crystals/chitosan nanobubbles composite hydrogel with improved gallic acid release property - Miral Javed; Hao Huang; Yueran Ma; Fatima-ezzahra Ettoumi; Lei Wang; Yanqun Xu; Hesham R. El-Seedi; Qiaomei Ru; Zisheng Luo (Food Chemistry, 2024)

Cultivating edible bio-inks: Elevating 3D printing with medium-internal-phase emulsion gel incorporating soybean protein isolate microgel particles - Jing-ru Song; Jia-rong Huang; Si-xu Ren; Hong-ze Zheng; Da-yong Zhou; Liang Song (Food Hydrocolloids, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Next-generation sequencing of cerebrospinal fluid for the diagnosis and monitoring of neurocysticercosis - Jiexi Wen; Wen Su; Lei Zhang; Ru Huang; Jian Yin; Kai Li (Acta Neurologica Belgica, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Characterization of CM-Dil-labeled Muse cells in culture and in skin wounds in rats - Yan-yun Cao; Jing Ning; Ru-zhi Zhang; Kang Ge; Ting-ting Huang (Cell and Tissue Banking, 2024)

Density affects plant size in the Gobi Desert - Yonghua Li; Zhiming Xin; Bin Yao; Ruibing Duan; Xue Dong; Yanfeng Bao; Xinle Li; Yuan Ma; Yaru Huang; Fengmin Luo; Xing Li; Xu Wei; et al. (Science of The Total Environment, 2024)

Mechanism of enhanced microalgal biomass and lipid accumulation through symbiosis between a highly succinic acid-producing strain of Escherichia coli SUC and Aurantiochytrium sp. SW1 - Mei-Yu Zhang; Xin-Ru Xu; Ru-Ping Zhao; Chao Huang; Yuan-Da Song; Zi-Tong Zhao; Yu-Bin Zhao; Xiao-Jie Ren; Xin-He Zhao (Bioresource Technology, 2024)

Organ-specific off-target effects of Pim/ZIP kinase inhibitors suggest lack of contractile Pim kinase activity in prostate, bladder, and vascular smooth muscle - Sheng Hu; Moritz Trieb; Ru Huang; Alexander Tamalunas; Patrick Keller; Melanie Götz; Raphaela Waidelich; Christian G. Stief; Martin Hennenberg (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Smooth muscle contraction by Pim kinases and ZIPK has been suggested, but evidence for lower urinary tract organs or using Pim-selective inhibitor concentrations is not yet available. Here, we assessed effects of the Pim inhibitors AZD1208 and TCS PIM-1 and the dual ZIPK/Pim inhibitor HS38 on contractions of human prostate and bladder tissues and of porcine interlobar arteries. Human tissues were obtained from radical prostatectomy and radical cystectomy and renal interlobar arteries from pigs. Contractions were studied in an organ bath. Noradrenaline-, phenylephrine- and methoxamine-induced contractions were reduced (up to > 50%) with 500-nM AZD1208 in prostate tissues and to lesser degree and not consistently with all agonists in interlobar arteries. A total of 100-nM AZD1208 or 500-nM TCS PIM-1 did not affect agonist-induced contractions in prostate tissues. Decreases in agonist-induced contractions with 3-µM HS38 in prostate tissues and interlobar arteries were of small extent and did not occur with each agonist. Carbachol-induced contractions in detrusor tissues were unchanged with AZD1208 (500 nM) or HS38. Electric field stimulation–induced contractions were not affected with AZD1208 or HS38 in any tissue, but slightly reduced with 500-nM TCS PIM-1 in prostate tissues. Concentration-dependent effects of Pim inhibitors suggest lacking Pim-driven smooth muscle contraction in the prostate, bladder, and interlobar arteries but point to organ-specific functions of off-targets. Procontractile functions of ZIPK in the prostate and interlobar arteries may be limited and are lacking in the detrusor.

Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2024)
The health of the host is significantly influenced by the gut microbiota. Penaeus vannamei (white shrimp) is one of the most profitable aquaculture species globally. Synbiotics are typically used as a beneficial diet supplement for raising aquaculture species’ growth capacities and enhancing immunity against pathogenicity. However, the effects of synbiotics on the white shrimp intestinal microbiota remain poorly understood. In the present study, we targeted the V3–V4 region of 16S rRNA genes to analyze the effects of synbiotics on white shrimp gut microbiota. Dietary synbiotics, having Lactobacillus acidophilus , and Moringa oleifera leaf extract were added to the white shrimps’ feed in various proportions in the present study. In total, 490 operational taxonomic units yielding 23 phyla, 41 classes, 94 orders, 151 families, and 250 genera of microorganisms were obtained. The diet containing L. acidophilus at 1 × 10 7 CFU/g and M. oleifera at 2.5 g/kg led to an increase in the relative abundance of beneficial microorganisms through a significant decrease in the α diversity. Moreover, it upregulated several physiological pathways such as carbohydrate metabolism, signal transduction, lipid metabolism, nucleotide metabolism, amino acid metabolism, and environmental adaptation, which led to the upregulation of the AMPK, MAPK, P13K-Akt, lysosome, peroxisome, and ferroptosis signaling pathways; this enhanced growth and immunity in white shrimp. Whether a single species or a combination of different microorganisms improves growth and immunity remains unclear till now. Nevertheless, our results will facilitate further in-depth investigation into beneficial microbial communities for upliftment of white shrimp aquaculture.

Effects of Different Intensities and Wavelengths of Light on the Growth of Juvenile Tridacna noae - Rod Ping-Tsan Lee; Yu-Ru Lin; Chih-Yang Huang; Fan-Hua Nan (Molluscan Research, 2024)

The apoptosis of Chlorella vulgaris and the release of intracellular organic matter under metalimnetic oxygen minimum conditions - Ru Wang; Shuo Wang; Ruihua Cao; Jingru Han; Tinglin Huang; Gang Wen (Science of The Total Environment, 2024)

Effect of marine heatwaves on juvenile greater amberjack (Seriola dumerili) - Yali Tian; Hang Li; Dongying Zhang; Chen Wang; Ruijuan Hao; Xiaoying Ru; Qin Hu; Yang Huang; Chunhua Zhu (Marine Environmental Research, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

Tree ring oxygen isotope in Asia - Chenxi Xu; Ru Huang; Wenling An; Qingyu Zhao; Yaru Zhao; Junbo Ren; Yucheng Liu; Zhengtang Guo (Global and Planetary Change, 2024)

Effects of freezing methods on physicochemical properties, protein/fat oxidation and odor characteristics of surimi gels with different cross-linking degrees - Xiaoying Luo; Kang Huang; Yongxin Niu; Xu Zhang; Yueqi An; Ru Liu; Shanbai Xiong; Yang Hu (Food Chemistry, 2024)

Bacillus velezensis HY19 as a sustainable preservative in post-harvest citrus (Citrus reticulata Blanco L.) fruit management - Suping Li; Jingyu Hu; Shiqi Ning; Wei Li; Ru Jiang; Jianguo Huang; Yong Li (Food Control, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

Nitrite acts as the key “switch” governing the free nitrous acid pretreatment in anaerobic digestion: A comprehensive mechanism of abiotic, bioinformatics and bioenergetics effects - Zhibang Han; Ru Fang; Xueting Wang; Guangchen Huang; Dong Wu; Jun Tai; Bing Xie; Yinglong Su; Jingyang Luo; Gang Zhao; Ming Jiang (Chemical Engineering Journal, 2024)

High-strength ionic hydrogel constructed by metal-free physical crosslinking strategy for enhanced uranium extraction from seawater - Yuan-Hao Wang; Yu-Qin Xiang; Qian Huang; Xiao-Lan Yang; Shuang-Long Wang; Yue-Ru Zhou; Song Qin; Ling-Qiong Gou; Guo-Hong Tao; Ling He (Chemical Engineering Journal, 2024)

Supramolecular fluorescence sensor array used for the analysis of tyrosine kinase inhibitors in biological fluids and cell imaging - Hong-Ling Yi; Ru-Pei Yang; Qing Tang; Zhu Tao; Ying Huang (Analytica Chimica Acta, 2024)

Research on the impact of manufacturing virtual agglomeration on green total factor productivity of enterprises under the Sustainable Development Goals - Qing Zhang; Shaofeng Ru; Hongyun Huang (Environmental Science and Pollution Research, 2023)

Insights into greenhouse gas emissions from a wastewater treatment plant in vulnerable water areas of China - Jiemiao Ma; Xiaojing Ni; Chen Cai; Yuewu Da; Kan Hu; Ru Guo; Jia Liu; Kaiming Peng; Erwu Liu; Xiangfeng Huang (Science of The Total Environment, 2023)

Artificial light at night, MRI-based measures of brain iron deposition and incidence of multiple mental disorders - Jianbo Jin; Wenxing Han; Teng Yang; Zhihu Xu; Jin Zhang; Ru Cao; Yuxin Wang; Jiawei Wang; Xin Hu; Tiantian Gu; Fan He; Jing Huang; et al. (Science of The Total Environment, 2023)

Magmatic–hydrothermal evolution of the Koktokay No. 3 pegmatite, Altai, northwestern China: Constraints from in situ boron isotope and chemical compositions of tourmaline - Rong Yin; Xiao-Long Huang; Ru-Cheng Wang; Gang-Jian Wei; Yi-Gang Xu; Yu Wang; Xiao-Ming Sun; Le Zhang; Xiao-Ping Xia (Lithos, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Application of lipid and polymeric-based nanoparticles for treatment of inner ear infections via XGBoost - Jie Zhang; Ru Chen; Shuainan Chen; Die Yu; Dalia H. Elkamchouchi; Mohammed S. Alqahtani; Hamid Assilzadeh; Zhongguan Huang; Yideng Huang (Environmental Research, 2023)

Moisture-induced secondary inorganic aerosol formation dominated the light absorption enhancement of refractory black carbon at an urban site in northwest China - Ziqi Chen; Yunfei Wu; Xin Wang; Ru-jin Huang; Renjian Zhang (Atmospheric Environment, 2023)

A Potential Association of Zinc Deficiency and Tyrosine Kinase Inhibitor-Induced Hand-Foot Skin Reaction - Chun-Nan Yeh; Wen-Kuan Huang; Chun-Wei Lu; Chiao-Ping Chen; Sheng-Hsuan Lin; Yi-Ru Pan; Chiao-En Wu (Biological Trace Element Research, 2023)

Tree ring derived summer temperature variability over the past millennium in the western Himalayas of northern Pakistan - Fayaz Asad; Haifeng Zhu; Tabassum Yaseen; Ru Huang; Mukund Palat Rao (Frontiers of Earth Science, 2023)

Inter-brain neural mechanism and influencing factors underlying different cooperative behaviors: a hyperscanning study - Qingming Liu; Huimin Cui; Bincan Huang; Yingying Huang; Huimeng Sun; Xinyi Ru; Mingming Zhang; Wei Chen (Brain Structure and Function, 2023)

Urban greenspace types influence the microbial community assembly and antibiotic resistome more in the phyllosphere than in the soil - Xin-Rong Huang; Roy Neilson; Le-Yang Yang; Jing-Jun Deng; Shu-Yi-Dan Zhou; Hu Li; Yong-Guan Zhu; Xiao-Ru Yang (Chemosphere, 2023)

Recent understanding of stress response on muscle quality of fish: From the perspective of industrial chain - Tonghao Zhang; Liangzi Zhang; Tao Yin; Juan You; Ru Liu; Qilin Huang; Liu Shi; Lan Wang; Tao Liao; Weisheng Wang; Huawei Ma (Trends in Food Science & Technology, 2023)

Decreased levels of perfluoroalkyl substances in patients receiving hemodialysis treatment - Jih-Kai Huang; Yun-Shiuan Chuang; Ping-Hsun Wu; Chi-Jung Tai; Jye-Ru Lin; Mei-Chuan Kuo; Yi-Wen Chiu; Ping-Chi Hsu; Ming-Tsang Wu; Samira Salihovic; Yi-Ting Lin (Science of The Total Environment, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Upcycling soybean pulp for sustainable amino acid and subsequent protein biomanufacturing via a one-pot thermophilic protease cascade treatment - Ronnie G. Gicana; Min-Hsuan Huang; Tony Z. Jia; Yin-Ru Chiang; Po-Hsiang Wang (Chemical Engineering Journal, 2023)

Human TRMT1 catalyzes m2G or m22G formation on tRNAs in a substrate-dependent manner - Qing-Ping Xiong; Jing Li; Hao Li; Zhi-Xuan Huang; Han Dong; En-Duo Wang; Ru-Juan Liu (Science China Life Sciences, 2023)

Microplastics in coastal farmed oyster (Crassostrea angulata) shells: Abundance, characteristics, and diversity - Chih-Feng Chen; Yun-Ru Ju; Yee Cheng Lim; Ming-Huang Wang; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2023)

Effects of contrasting tillage managements on the vertical distribution of plant- and microbial-derived carbon in rice paddy - Jian-Ying Qi; Xiang-Bin Yao; Mei-Yang Duan; Xiang-Wen Huang; Mei-Yi Fan; Ya Yang; Hao-Wen Luo; Xiang-Ru Tang (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

From arc accretion to within-plate extension: Geochronology and geochemistry of the Neoproterozoic magmatism on the northern margin of the Yangtze Block - Yu Huang; Xiao-Lei Wang; Jun-Yong Li; Ru-Cao Li; De-Hong Du; Chang-Hong Jiang; Lin-Sen Li; Ning Ding (Precambrian Research, 2023)

Phloroglucinol derivatives, coumarins and an alkaloid from the roots of Evodia lepta Merr. - Xiao-Ying Ding; Jun-Ru Wen; Wei-Yao Lin; Guo-Yong Huang; Qian Feng; Lixin Duan; Shi-Jie Zhang; Zhongqiu Liu; Rong-Rong Zhang; Ying Wang (Phytochemistry, 2023)

Isolation and identification of 3,4-seco-labdane diterpenoids from Callicarpa nudiflora and investigation of their cytotoxicity against HepG2 cells - Qian-Qian Chen; Ming-Hui Fan; Hong-Tao Xu; Le-Yi Huang; Jin-Ling Liu; Shan-Shan Zhang; Ru-Ru Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

CDN1163, a SERCA activator, causes intracellular Ca2+ leak, mitochondrial hyperpolarization and cell cycle arrest in mouse neuronal N2A cells - Yi-Ping Huang; Wen-Wei Huang; Kun-Feng Tsai; Lian-Ru Shiao; Zih-He Yang; Shao-Yun Tseng; Yu-Hsien Lin; Cing-Yu Chen; Paul Chan; Yuk-Man Leung (NeuroToxicology, 2023)

Targeting STING-mediated pro-inflammatory and pro-fibrotic effects of alveolar macrophages and fibroblasts blunts silicosis caused by silica particles - Liang Ou; Peng Zhang; Zhengpeng Huang; Yuxing Cheng; Qianru Miao; Ru Niu; Yuxin Hu; Ying Chen (Journal of Hazardous Materials, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Effects of exposure to chlorinated paraffins on human health: A scoping review - Jing-Wen Huang; Ya-Ying Bai; Mohammed Zeeshan; Ru-Qing Liu; Guang-Hui Dong (Science of The Total Environment, 2023)

First transcriptome profiling in gill and hepatopancrease tissues of Metapenaeus ensis in response to acute ammonia-N stress - Yun-Dong Li; Meng-Ru Si; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Li-Shi Yang; Jian-Hua Huang; Fa-Lin Zhou (Fish & Shellfish Immunology, 2023)

A marine lipopeptides-producing Bacillus amyloliquefaciens HY2-1 with a broad-spectrum antifungal and antibacterial activity and its fermentation kinetics study - Lin-ru Huang; Xiao-ning Ling; Shuai-ying Peng; Ming-hui Tan; Lu-qi Yan; Ying-yin Liang; Gang-hui Li; Kun-tai Li (World Journal of Microbiology and Biotechnology, 2023)

Application of machine learning to the Vs-based soil liquefaction potential assessment - Qi-ru Sui; Qin-huang Chen; Dan-dan Wang; Zhi-gang Tao (Journal of Mountain Science, 2023)

Soil extracellular enzymes characteristics and their controlling factors along the elevation gradient in Qinghai-Tibet Plateau, China - Yan-xia Pan; Xin-rong Li; Zeng-ru Wang; Li Feng; Lei Huang; Bing-yao Wang; Jing-yao Sun (Applied Soil Ecology, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Xanthine-derived reactive oxygen species exacerbates adipose tissue disorders in male db/db mice induced by real-ambient PM2.5 exposure - Leijian Chen; Huankai Li; Yi Ru; Yuanyuan Song; Yuting Shen; Lifang Zhao; Gefei Huang; Yi Chen; Zenghua Qi; Ruijin Li; Chuan Dong; Jiacheng Fang; et al. (Science of The Total Environment, 2023)

Nonagricultural emissions enhance dimethylamine and modulate urban atmospheric nucleation - Yunhua Chang; Qingyang Ling; Xinlei Ge; Xiangyang Yuan; Shengqian Zhou; Kai Cheng; Jianjiong Mao; Dandan Huang; Qingyao Hu; Jun Lu; Shijie Cui; Yaqing Gao; et al. (Science Bulletin, 2023)

Enhancement of Zn-N-C charge-directed rearrangement for high-performance selectivity of heavy metal ions in capacitive deionization - Xinhua Huang; Zhirou Wang; Xiaonan Li; Dongyin Qin; Meiyue Jin; Yuzudi Tong; Ru Li (Desalination, 2023)

Highly sensitive plasmonic biosensor for hepatitis B virus DNA based on the surface etching of the active helical gold nanorods - Ru Cheng; Liang Tong Li; Min Huang; Fu Zhu; Qian Li; Hui Liu; Jie Gao; Xiao Hui Zhao; Fu Kang Luo; Jian Wang (Chemical Engineering Journal, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Comparative Physiological and Transcriptomic Analysis Provide New Insights of Crucial Pathways and Genes Regulating Kenaf Salt Tolerance - Yali Hu; Zengqiang Li; Meiqiong Tang; Dengjie Luo; Muhammad Haneef Kashif; Shan Cao; Caijin Wang; Jiao Yue; Zhen Huang; Jiao Pan; Xia Wu; Qijing Wu; et al. (Journal of Plant Growth Regulation, 2023)

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Valorization of soybean pulp for sustainable α-ketoisocaproate production using engineered Bacillus subtilis whole-cell biocatalyst - Eugene Huang; Jhen-Sheng Yan; Ronnie G. Gicana; Yin-Ru Chiang; Fang-I Yeh; Chieh-Chen Huang; Po-Hsiang Wang (Chemosphere, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

An extended SW-TES algorithm for land surface temperature and emissivity retrieval from ECOSTRESS thermal infrared data over urban areas - Chen Ru; Si-Bo Duan; Xiao-Guang Jiang; Zhao-Liang Li; Cheng Huang; Meng Liu (Remote Sensing of Environment, 2023)

Flexible, biocompatible, degradable silk fibroin based display - Zijie Xu; Zhi He; Jiani Huang; Wu Qiu; Leo N.Y. Cao; Aniruddha Patil; Bo-Ru Yang; Xiang Yang Liu; Wenxi Guo (Chemical Engineering Journal, 2023)

Electrochemical etching induced high-valence cobalt with defects site for boosting electrochemical water splitting - Hongmei Gao; Jiaqi Liu; Zijin Zhang; Yuxuan Lu; Ru Chen; Yu-Cheng Huang; Chao Xie; Mengyi Qiu; Tianyu Wu; Jinbo Wang; Yubin Jiang; Chung-Li Dong; et al. (Chemical Engineering Journal, 2023)

Seasonal changes in diurnal rainfall over Sri Lanka and possible mechanisms - Wan-Ru Huang; Suranjith Bandara Koralegedara; Po-Han Tung; Tzu-Yang Chiang (Atmospheric Research, 2023)

Circulating polyunsaturated fatty acids, fish oil supplementation, and risk of incident dementia: a prospective cohort study of 440,750 participants - Yu He; Shu-Yi Huang; Hui-Fu Wang; Wei Zhang; Yue-Ting Deng; Ya-Ru Zhang; Qiang Dong; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (GeroScience, 2023)

Extreme cooling of 12.5 °C triggered by Typhoon Fungwong (2008) - Zhe-Wen Zheng; Jia-Yi Lin; Ganesh Gopalakrishnan; Yi-Rui Chen; Doon-Jing Doong; Chung-Ru Ho; Quanan Zheng; Chau-Ron Wu; Chen-Fen Huang (Ocean Modelling, 2023)

Effect of nanoclay supported nanosilver on the growth inhibition of aquatic pathogens and immunomodulatory effect in Penaeus vannamei - Zhen-Hao Liao; Huai-Ting Huang; Yu-Ru Lin; Chi-Yun Hu; Yu-Hsuan Kai; Jiang-Jen Lin; Fan-Hua Nan (Fish & Shellfish Immunology, 2023)

Characterization of microbial community, ecological functions and antibiotic resistance in estuarine plastisphere - Le-Yang Yang; Xin-Rong Huang; Roy Neilson; Shu-Yi-Dan Zhou; Zhao-Lei Li; Xiao-Ru Yang; Xiao-Xuan Su (Science of The Total Environment, 2023)

Plant identity shapes phyllosphere microbiome structure and abundance of genes involved in nutrient cycling - Jian Li; Ming-Kang Jin; Roy Neilson; Shi-Lin Hu; Yi-Jia Tang; Zhao Zhang; Fu-Yi Huang; Jing Zhang; Xiao-Ru Yang (Science of The Total Environment, 2023)

Direct emissions of particulate glyoxal and methylglyoxal from biomass burning and coal combustion - Ting Wang; Ru-Jin Huang; Lu Yang; Wenting Dai; Haiyan Ni; Yuquan Gong; Jie Guo; Haobin Zhong; Chunshui Lin; Wei Xu (Science of The Total Environment, 2023)

Gelation properties of tofu induced by different coagulants: Effects of molecular interactions between nano-sized okara dietary fiber and soybean proteins - Ikram Ullah; Ramy M. Khoder; Tao Yin; Juan You; Qilin Huang; Ru Liu; Shanbai Xiong (Food Chemistry, 2023)

Carnosic acid attenuated cytochrome c release through the mitochondrial structural protein Mic60 by PINK1 in SH-SY5Y cells - Chia-Yuan Lin; Yi-Chen Huang; Chi-Rei Wu; Han-Ting Wu; Ru-Huei Fu; Chia-Wen Tsai (Food and Chemical Toxicology, 2023)

Chronic exposure to di(2-ethylhexyl) phthalate (DEHP) weakens innate immunity and leads to immunosenescence in C. elegans - Pei-Ling Yen; Cai-Ru Yang; Mei-Lun Huang; Ting-An Lin; Vivian Hsiu-Chuan Liao (Environmental Toxicology and Pharmacology, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

How Comamonas testosteroni and Rhodococcus ruber enhance nitrification in the presence of quinoline - Ge Zhu; Haiyun Zhang; Ru Yuan; Meng Huang; Fei Liu; Mo Li; Yongming Zhang; Bruce E. Rittmann (Water Research, 2023)

Synthesis of cationic polymer decorated with halogen for highly efficient trapping 99TcO4-/ReO4- - You-Gan Wang; Qing-Hua Hu; Juan Huang; Wei Jiang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

Ultrastructure and distribution of antennal sensilla of Bombus terrestris (Hymenoptera: Apidae) - Xi Huang; Xi-lian Xu; Ru-xu Li; Su Wang; Li-xia Tian (Zoologischer Anzeiger, 2023)

Water–energy–carbon synergies and trade-offs: A daily nexus analysis for wastewater treatment plants - Xiaojing Ni; Xiangfeng Huang; Ru Guo; Jinhui Wang; Kaiming Peng; Wei Zhang; Yuyu Zhu; Weilan Yang; Liya Wang; Chen Cai; Jia Liu; Erwu Liu (Resources, Conservation and Recycling, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Luteolin ameliorates palmitate-induced lipotoxicity in hepatocytes by mediating endoplasmic reticulum stress and autophagy - Chun-Yin Huang; Haw-Wen Chen; Chia-Wen Lo; Yu-Ru Wang; Chien-Chun Li; Kai-Li Liu; Chong-Kuei Lii (Food and Chemical Toxicology, 2023)

Air pollution, greenness and risk of overweight among middle-aged and older adults: A cohort study in China - Wenxing Han; Zhihu Xu; Xin Hu; Ru Cao; Yuxin Wang; Jianbo Jin; Jiawei Wang; Teng Yang; Qiang Zeng; Jing Huang; Guoxing Li (Environmental Research, 2023)

Narrowing fossil fuel consumption in the Indian road transport sector towards reaching carbon neutrality - M.S. Hossain; Yan Ru Fang; Teng Ma; Chen Huang; Wei Peng; Johannes Urpelainen; Chetan Hebbale; Hancheng Dai (Energy Policy, 2023)

Recyclable nanocomposites for carbon dioxide fixation and membrane separation using waste polycarbonate - Ying-Chi Huang; Li-Fan Chen; Yu-Hsiang Huang; Chien-Chieh Hu; Chien-Hsin Wu; Ru-Jong Jeng (Chemical Engineering Journal, 2023)

Efficient microalgal lipid production driven by salt stress and phytohormones synergistically - Zi-Yan Yang; Kai-Xuan Huang; Yu-Ru Zhang; Lei Yang; Jin-Long Zhou; Qiao Yang; Feng Gao (Bioresource Technology, 2023)

Application of hybrid machine learning model for flood hazard zoning assessments - Jhih-Huang Wang; Gwo-Fong Lin; Yun-Ru Huang; I-Hang Huang; Chieh-Lin Chen (Stochastic Environmental Research and Risk Assessment, 2023)

Citric acid-based deep eutectic solvent (CA-DES) as a new soil detergent for the removal of cadmium from coking sites - Jie Qian; Ying-hua Li; Fei Su; Ji-guo Wu; Jia-ru Sun; Tian-ci Huang (Environmental Science and Pollution Research, 2023)

Contrasting treeline dynamics of pine and birch in response to climate warming in the Karakoram - Munawar Ali; Shalik Ram Sigdel; Xiangyu Zheng; Fayaz Asad; Ru Huang; Haifeng Zhu; Sher Muhammad; Iqtidar Hussain; Saulat Hussain; J. Julio Camarero; Eryuan Liang (Trees, 2022)

Cryo-EM structures reveal the dynamic transformation of human alpha-2-macroglobulin working as a protease inhibitor - Xiaoxing Huang; Youwang Wang; Cong Yu; Hui Zhang; Qiang Ru; Xinxin Li; Kai Song; Min Zhou; Ping Zhu (Science China Life Sciences, 2022)

The central role of GmGLP20.4 in root architecture modifications of soybean under low-nitrogen stress - Wei Wang; Jiajia Li; Muhammad Nadeem; Jianxin Wang; Ru Huang; Qian Liu; Wenqiao Fan; Haowei Zheng; Long Yan; Xiaobo Wang (Theoretical and Applied Genetics, 2022)

PITPNC1 promotes the thermogenesis of brown adipose tissue under acute cold exposure - Guoqing Tang; Chengxin Ma; Liangkui Li; Shaoyan Zhang; Fengsheng Li; Jin Wu; Yesheng Yin; Qing Zhu; Yan Liang; Ru Wang; He Huang; Tong-Jin Zhao; et al. (Science China Life Sciences, 2022)
Brown adipose tissue (BAT) plays an essential role in non-shivering thermogenesis. The phosphatidylinositol transfer protein, cytoplasmic 1 (PITPNC1) is identified as a lipid transporter that reciprocally transfers phospholipids between intracellular membrane structures. However, the physiological significance of PITPNC1 and its regulatory mechanism remain unclear. Here, we demonstrate that PITPNC1 is a key player in thermogenesis of BAT. While Pitpnc1 −/− mice do not differ with wildtype mice in body weight and insulin sensitivity on either chow or high-fat diet, they develop hypothermia when subjected to acute cold exposure at 4°C. The Pitpnc1 −/− brown adipocytes exhibit defective β-oxidation and abnormal thermogenesis-related metabolism pathways in mitochondria. The deficiency of lipid mobilization in Pitpnc1 −/− brown adipocytes might be the result of excessive accumulation of phosphatidylcholine and a reduction of phosphatidic acid. Our findings have uncovered significant roles of PITPNC1 in mitochondrial phospholipid homeostasis and BAT thermogenesis.

Discovery of the oncogenic MDM2, a direct binding target of berberine and a potential therapeutic, in multiple myeloma - Chuting Li; Ru Su; Xiuyuan Wang; Guiping Huang; Yanjun Liu; Juhua Yang; Zhao Yin; Chunming Gu; Jia Fei (Functional & Integrative Genomics, 2022)

Winter–summer contrast of the 1990s decadal change in relation to Afro–Asian monsoons - Chi-Hua Wu; Pei-Chia Tsai; Wan-Ru Huang; S.-Y. Simon Wang (Climate Dynamics, 2022)

Deletions in GSN gene associated with growth traits of four Chinese cattle breeds - Ao Qi; Wenxiu Ru; Yangkai Liu; Yu Yang; Jia Tang; Haiyan Yang; Shuling Yang; Kaixing Qu; Xianyong Lan; Chuzhao Lei; Bizhi Huang; Hong Chen (Molecular Genetics and Genomics, 2022)

Vibrio salinus sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll in the western Pacific Ocean - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2022)

Why empresses have more sons? Maternal instant social condition determines it - Yan-Peng Li; Wei Ding; Zhi-Pang Huang; Ru-Liang Pan; Na Li; Guo-Peng Ren; Liang-Wei Cui; Qing-hua Cai; Wen Xiao (Behavioral Ecology and Sociobiology, 2022)
Sexual selection echoed by the sex ratio is a critical issue in evolution and reproductive biology studies, and the second sex ratio (sex ratio at birth, SRB) is an important evaluation indicator for sex regulation. However, broad debates on sex ratio at birth exist due to the lack of a clear spatiotemporal genealogical database. This study explicitly tests the Trivers and Willard’s hypothesis stating that parents with good social conditions tend to show a male-biased SRB. Using a database of Chinese imperial families from 211BC to 1912 (2142 years) which avoids the spatiotemporal confusion of data thanks to its clear boundaries and long timespan, we found that a proportion of males at birth was 0.54. In particular, the results indicate that the empresses generated a significantly higher male-biased SRB than the concubines within the imperial harems (0.61 vs 0.53), while the SRB of concubines was not higher than ordinary people (0.53 vs 0.52). A significant difference of SRB before and after empress coronation (0.48 vs 0.65) was detected, indicating that the change to a higher social status is the leading cause of a biased SRB. These findings suggest that mothers with privileged instant social conditions tend to generate more boys than girls. In other words, a higher maternal social rank during the conception period, instead of rich resources, forms the primary mechanism regulating the SRB. Significance statement Adaptive sex ratio has been a debatable topic difficult to clearly verify since the publication of Trivers and Willard Hypothesis in 1973, which proposes that parents who have good conditions should produce more male offspring. The one reason is that the validity and sample size of the databases used contained unavoidable confounding noise, both genealogically and genetically. To overcome these issues, we specifically compiled a historical database of Chinese imperial families, which are characterized by a confined mating harem and unique eunuch system, guaranteeing biological and genetic purity with precise genealogical relationships and genetic linkages between the parents and the offspring. Thus, this is an extraordinary effort to clarify the hypotheses proposed by TWH and other hypotheses.

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

miR-211-3p enhances induction chemotherapy insensitivity by upregulating CSF2/CCL20/TNF signaling in hypopharyngeal squamous cell carcinoma - Lingwa Wang; Ru Wang; Tianqiao Huang; Yifan Yang; Ling Feng; Jugao Fang (Molecular Biology Reports, 2022)

Dataset-based assessment of heavy metal contamination in freshwater fishes and their health risks - Xiao-Bo Liu; Congtian Lin; Yang-Yu Wu; Hai-Ning Huang; Li-Ting Zhu; Ru Jiang; Qiansheng Huang (Environmental Science and Pollution Research, 2022)

High Levels of 25-OH-Vitamin D and Copper in Pregnant Women with Abnormal Glucose Challenge Test - Chien-Hua Chiang; Wan-Ju Kung; Chien-Hung Lee; Yeong-Hwa Zen; Cheng-Fa Lee; Hui-Ru Yang; Ching-Chiang Lin; Yeou-Lih Huang (Biological Trace Element Research, 2022)

Natural Feed Supplements Improve Growth, Non-Specific Immune Responses and Resistance against Vibrio alginolyticus in Lates calcarifer - Zhen-Hao Liao; Huai-Ting Huang; Yu-Ru Lin; Bo-Ying Chen; Yi-Fan Lee; Yuan-Heng Lin; Chieh-Yuan Chuang; Fan-Hua Nan (Journal of Marine Science and Engineering, 2022)
This study aimed to investigate the effects of dietary natural feed supplement on the growth performance, non-specific responses, and disease resistance in Lates calcarifer. Three commercial products (A, B, and C) containing a basal probiotic mixture were tested. Product A contained a basal mixture of Paenibacillus sp., Bacillus subtilis, Bacillus amyloliquefaciens, and Lactobacillus rhamnosus (107 cfu/g for each probiotic); product B contained additional Lactobacillus plantarum (1010 cfu/g); and product C contained additional soybean peptides (500 g/kg) and garlic powder (1 g/kg). Each product was supplemented into subject diets at dosages of 1 or 2 g/kg (designated as the A1, A2, B1, B2, C1, and C2 groups, respectively). Following an eight-week trial, growth parameters (specific growth rate and feed conversion ratio), non-specific immune responses (O2− production, phagocytic rate, and phagocytic index), and the results of a challenge test against Vibrio alginolyticus were evaluated. The results show that all probiotic supplement groups exhibited an improvement in growth performance compared to the control group (non-probiotic diet). In terms of non-specific immunity parameters, a significant improvement in O2− production was found in the C2 group, whereas significant improvements in phagocytic activity were found in all the B and C groups. The C2 group displayed optimal O2− production, phagocytic rate, and phagocytic index results. For the challenge test, the C groups showed higher Vibrio resistance than the other experimental groups and the control group. These results suggest that product C, given at dosages of 2 g/kg, may serve as a growth-promoting and immunostimulatory additive for the cultivation of Asian seabass.

First report of Capsicum frutescens endornavirus 1 infecting pepper in China - Ming-xia Gong; Hu Zhao; Xing Wu; Meng Wang; Zeng-jing Zhao; Zhi He; Ru-kui Huang; Jing-ping Sun; Ri-sheng Wang (Journal of Plant Pathology, 2022)

Inhibition of neurogenic contractions in renal arteries and of cholinergic contractions in coronary arteries by the presumed inhibitor of ADP-ribosylation factor 6, NAV2729 - Ru Huang; Bingsheng Li; Alexander Tamalunas; Raphaela Waidelich; Christian G. Stief; Martin Hennenberg (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)
NAV2729 is a presumed inhibitor of the monomeric GTPase ADP ribosylation factor 6 (ARF6) and inhibits smooth muscle contraction outside the cardiovascular system. Its effects on vascular smooth muscle contraction or a possible role of ARF6 in vasocontraction have not yet been examined. Here, we report effects of NAV2729 on neurogenic and agonist-induced contractions in renal interlobar and coronary arteries. Contractions of pig interlobar and coronary arteries were induced in an organ bath by agonists or by electric field stimulation (EFS). Owing to divergent characteristics of both vessel types, EFS-induced contractions were only examined in interlobar arteries, and contractions by agonists acting on muscarinic receptors only in coronary arteries. NAV2729 inhibited frequency-dependent EFS-induced contractions of interlobar arteries. The degree of inhibition was similar using 5 µM and 10 µM NAV2729. Inhibition of EFS-induced contractions was resistant to a nitric oxide synthase inhibitor and to diclofenac. The neurogenic and adrenergic character of EFS-induced contractions was confirmed by inhibition by tetrodotoxin and prazosin. In coronary arteries, NAV2729 (5 µM) inhibited concentration-dependent contractions induced by carbachol and methacholine. Contractions induced by α 1 -adrenergic agonists, endothelin-1, the thromboxane receptor agonist U46619, or serotonin remained unchanged by NAV2729 in both vessel types. NAV2729 inhibits neurogenic contractions in interlobar arteries and contractions induced by cholinergic agonists in coronary arteries. In both vessel types, NAV2729 does not inhibit contractions induced by receptor agonists other than those acting on muscarinic receptors. Addressing effects in other vessels and in other smooth muscle–rich organs merits further attention.

Imatinib-induced hepatotoxicity via oxidative stress and activation of NLRP3 inflammasome: an in vitro and in vivo study - Feng-Ru Huang; Wen-Tong Fang; Zi-Ping Cheng; Ye Shen; Dun-Jian Wang; Yong-Qing Wang; Lu-Ning Sun (Archives of Toxicology, 2022)

Moisture mediates temperature-growth couplings of high-elevation shrubs in the Tibetan plateau - Yang Han; Yafeng Wang; Bo Liu; Ru Huang; J. Julio Camarero (Trees, 2022)

circSVIL regulates bovine myoblast development by inhibiting STAT1 phosphorylation - Binglin Yue; Haiyan Yang; Jiyao Wu; Jian Wang; Wenxiu Ru; Jie Cheng; Yongzheng Huang; Xianyong Lan; Chuzhao Lei; Hong Chen (Science China Life Sciences, 2022)

NNMT is induced dynamically during beige adipogenesis in adipose tissues depot-specific manner - Ru Jia; Xiaojing Wei; Jianan Jiang; Zhao Yang; Jiaqi Huang; Jing Liu; Jianqun Yan; Xiao Luo (Journal of Physiology and Biochemistry, 2022)

Infectivity and antigenicity of pseudoviruses with high-frequency mutations of SARS-CoV-2 identified in Portugal - Hai-xin Wang; Li Zhang; Zi-teng Liang; Jian-hui Nie; Jia-jing Wu; Qian-qian Li; Ru-xia Ding; Yue Zhang; Guo-qing Chen; You-chun Wang; Hui-guo Wang; Wei-jin Huang (Archives of Virology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has had a major impact on global human health. During the spread of SARS-CoV-2, weakened host immunity and the use of vaccines with low efficacy may result in the development of more-virulent strains or strains with resistance to existing vaccines and antibodies. The prevalence of SARS-CoV-2 mutant strains differs between regions, and this variation may have an impact on the effectiveness of vaccines. In this study, an epidemiological investigation of SARS-CoV-2 in Portugal was performed, and the VSV-ΔG-G* pseudovirus system was used to construct 12 spike protein epidemic mutants, D614G, A222V+D614G, B.1.1.7, S477N+D614G, P1162R+D614G+A222V, D839Y+D614G, L176F+D614G, B.1.1.7+L216F, B.1.1.7+M740V, B.1.258, B.1.258+L1063F, and B.1.258+N751Y. The mutant pseudoviruses were used to infect four susceptible cell lines (Huh7, hACE2-293T-293T, Vero, and LLC-MK2) and 14 cell lines overexpressing ACE2 from different species. Mutant strains did not show increased infectivity or cross-species transmission. Neutralization activity against these pseudoviruses was evaluated using mouse serum and 11 monoclonal antibodies. The neutralizing activity of immunized mouse serum was not significantly reduced with the mutant strains, but the mutant strains from Portugal could evade nine of the 11 monoclonal antibodies tested. Neutralization resistance was mainly caused by the mutations S477N, N439K, and N501Y in the spike-receptor binding domain. These findings emphasize the importance of SARS-CoV-2 mutation tracking in different regions for epidemic prevention and control.

Complete genome sequencing and evolutionary analysis of hepatitis C virus subtype 6a, including strains from Guangdong Province, China - Ru Xu; Hao Wang; Jieting Huang; Min Wang; Qiao Liao; Zhengang Shan; Huishan Zhong; Xia Rong; Yongshui Fu (Archives of Virology, 2022)

Correction to: Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Genome-Wide Identification and Expression Profiling of the bHLH Transcription Factor Gene Family in Saccharum spontaneum Under Bacterial Pathogen Stimuli - Ahmad Ali; Talha Javed; Uroosa Zaheer; Jing-Ru Zhou; Mei-Ting Huang; Hua-Ying Fu; San-Ji Gao (Tropical Plant Biology, 2021)

Epigenetics in psoriasis: perspective of DNA methylation - Ying Luo; Keshen Qu; Le Kuai; Yi Ru; Keke Huang; Xiaoning Yan; Meng Xing (Molecular Genetics and Genomics, 2021)

Prediction of Metabolic Disorders Using NMR-Based Metabolomics: The Shanghai Changfeng Study - Qi Wu; Qing-xia Huang; Hai-luan Zeng; Shuai Ma; Huan-dong Lin; Ming-feng Xia; Hui-ru Tang; Xin Gao (Phenomics, 2021)

Unexpected climate variability inferred from a 380-year tree-ring earlywood oxygen isotope record in the Karakoram, Northern Pakistan - Haifeng Zhu; Ru Huang; Fayaz Asad; Eryuan Liang; Achim Bräuning; Xuezhen Zhang; Binod Dawadi; Wenmin Man; Jussi Grießinger (Climate Dynamics, 2021)

Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Vibrio nitrifigilis sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2021)

Purinergic smooth muscle contractions in the human prostate: estimation of relevance and characterization of different agonists - Annabel Spek; Bingsheng Li; Beata Rutz; Anna Ciotkowska; Ru Huang; Yuhan Liu; Ruixiao Wang; Frank Strittmatter; Raphaela Waidelich; Christian G. Stief; Martin Hennenberg (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
Non-adrenergic prostate smooth muscle contractions may account for the limited effectiveness of α 1 -adrenoceptor antagonists, which are the first-line option for medical treatment of voiding symptoms suggestive of benign prostatic hyperplasia. In non-human prostates, purinergic agonists induce contractions reaching similar magnitudes as α 1 -adrenergic contractions. However, evidence for the human prostate is highly limited, and pointed to much weaker purinergic contractions. Here, we examined contractions of different purinergic agonists in human prostate tissues. Tissues were obtained from radical prostatectomy. Contractions were studied in an organ bath, and expression of purinergic receptors was studied by RT-PCR. Electric field stimulation (EFS)–induced contractions amounted to 104% of KCl-induced contractions (95% CI: 84–124%). From all tested agonists, only ATP induced concentration-dependent contractions, reaching an average maximum of 18% (12–24%) of KCl. Maximum tensions following application of other agonists averaged to 7.1% of KCl for α,β-methylene-ATP (1.8–12.4%), 3.9% for β,γ-methylene-ATP (2.0–5.4%), 3.1% for 2-methylthio-ATP (− 0.1–6.3%), and 5.1% for ATPγS (1.0–9.2%). Responses were not affected by the P2X antagonist NF023 or the P2Y antagonist PPADS. mRNA expression of P2X1-4 correlated with expression of a marker for catecholaminergic nerves, although neither ATP, NF023, nor PPADS changed EFS-induced contractions. Correlation between expression of receptors and the smooth muscle marker calponin was not observed. Our findings point to a low relevance of purinergic contractions in the human prostate, compared to other contractile stimuli in the human prostate and compared to purinergic contractions in non-human prostates. Purinergic contractions in the human prostate are not sensitive to NF023 or PPADS.

First report of Athelia rolfsii causing collar rot of Phalaenopsis orchid in Taiwan - Shih-Ya Chiu; Yi-Ru Lai; Wen-Shi Tsai; Chien-Jui Huang (Journal of Plant Pathology, 2021)

TRIP13 promotes the proliferation and invasion of lung cancer cells via the Wnt signaling pathway and epithelial–mesenchymal transition - Zhi-Han Li; Lei Lei; Liang-Ru Fei; Wen-Jing Huang; Yi-Wen Zheng; Mai-Qing Yang; Zhao Wang; Chen-Chen Liu; Hong-Tao Xu (Journal of Molecular Histology, 2021)

A comprehensive integrated transcriptome and metabolome analyses to reveal key genes and essential metabolic pathways involved in CMS in kenaf - Meiqiong Tang; Zengqiang Li; Dengjie Luo; Fan Wei; Muhammad Haneef Kashif; Hai Lu; Yali Hu; Jiao Yue; Zhen Huang; Wenye Tan; Ru Li; Peng Chen (Plant Cell Reports, 2021)

Characteristics of methane emissions in the Living Water Garden in Chengdu City from 2012 to 2017 - Ru Xue; Xiaoling Liu; Xiaoying Fu; Hongbing Luo; Ke Zhang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Xiaoting Li; Shuzhi Fu; Aiping Pu; et al. (Environmental Science and Pollution Research, 2020)

Comparative Variations of Extractive Nitrogenous Components and Quality in Fresh Muscle and Dried Product of Rabbitfish ( Siganus fuscescens ) in Taiwan - Yu-Ru Huang; Wan-Yi Huang; Hsiao-Chin Jen; Bi-Yu Liu; Ken-Meng Huang; Deng Fwu Hwang (Journal of Aquatic Food Product Technology, 2020)

First report of Acidovorax avenae subsp. avenae causing bacterial leaf blight of tea in Taiwan - I-Hsin Sung; Yi-Ru Lai; Chien-Jui Huang (Journal of Plant Pathology, 2020)

Correlation between the ovarian status and the androgen sensibility in the cultured Japanese eel, Anguilla japonica - Yung-Sen Huang; Xuan-Hao Wu; Pei-Syuan Huang; Guan-Ru Chen (Fish Physiology and Biochemistry, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Pure qP-wave least-squares reverse time migration in vertically transverse isotropic media and its application to field data - Jian-Ping Huang; Xin-Ru Mu; Zhen-Chun Li; Qing-Yang Li; Shuang-Qi Yuan; Yun-Dong Guo (Applied Geophysics, 2020)

Characterization of a Phosphatidylserine Synthase of Vibrio parahaemolyticus - Ru-Yin Huang; Chia-Yin Lee (Current Microbiology, 2020)

Thioredoxin-Interacting Protein (TXNIP) Regulates Parkin/PINK1-mediated Mitophagy in Dopaminergic Neurons Under High-glucose Conditions: Implications for Molecular Links Between Parkinson’s Disease and Diabetes - Cun-Jin Su; Zhu Shen; Ru-Xiao Cui; Ya Huang; De-Lai Xu; Feng-Lun Zhao; Jie Pan; Ai-Ming Shi; Tong Liu; Yun-Li Yu (Neuroscience Bulletin, 2020)

The effective use of camera traps to document the northernmost distribution of the western black crested gibbon in China - Yi-Hao Fang; Yan-Peng Li; Guo-Peng Ren; Zhi-Pang Huang; Liang-Wei Cui; Li-Xiang zhang; Paul A. Garber; Ru-Liang Pan; Wen Xiao (Primates, 2020)

Applying multivariate statistics for identification of groundwater chemistry and qualities in the Sugan Lake Basin, Northern Qinghai-Tibet Plateau, China - Juan Xiang; Jun-ju Zhou; Jun-cang Yang; Mei-hua Huang; Wei Feng; Qiao-qiao Li; Dong-xiang Xue; Ya-ru Zhao; Guo-feng Zhu (Journal of Mountain Science, 2020)

Modified stepwise mini-incision microdissection testicular sperm extraction: a useful technique for patients with a history of orchidopexy affected by non-obstructive azoospermia - Peng Li; Chen-cheng Yao; Er-lei Zhi; Yuan Xu; Zhong Wan; Ying-chuan Jiang; Yu-hua Huang; Yue-hua Gong; Hui-xing Chen; Ru-hui Tian; Chao Yang; Liang-yu Zhao; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Development of Human in vitro Brain-blood Barrier Model from Induced Pluripotent Stem Cell-derived Endothelial Cells to Predict the in vivo Permeability of Drugs - Yuan Li; Xueying Sun; Houfu Liu; Liang Huang; Guofeng Meng; Yu Ding; Wenji Su; Jiaqi Lu; Sophie Gong; Georg C. Terstappen; Ru Zhang; Wandong Zhang (Neuroscience Bulletin, 2019)

Climatology and change of extreme precipitation events in Taiwan based on weather types - Yi‐chao Wu; S.‐Y. Simon Wang; Yi‐Chiang Yu; Chu‐Ying Kung; An‐Hsiang Wang; Sebastian A. Los; Wan‐Ru Huang (International Journal of Climatology, 2019)
Taiwan's most significant natural hazards are caused by hydrological extremes resulting from excessive precipitation. The threat of extreme precipitation is posed by several different types of weather patterns that affect Taiwan. This study examined the bi‐decadal changes in rainfall by defining an extreme precipitation occurrence (EPO) for a range of event durations from 1 to 24 hr. Three major weather types affecting EPO in Taiwan were identified from 1993 to 2015: the front type consisting of either a frontal zone or convective systems developing with an apparent Meiyu cloudband, diurnal rainfall events when no apparent synoptic features are present, and a tropical cyclone (TC) type according to the maximum sustained wind radius of a TC. Results show that TC‐type events have the greatest overall contribution to EPO at longer (>6 hr) durations. Diurnal/afternoon convection events contribute most to the shorter ( 6 hr) EPO associated with the TC‐type events in summer. The distinction between EPO trends for the entire island of Taiwan and for the Taipei metropolitan area alone (northern Taiwan, population of 7 million) were compared, and an intriguing interannual variation is reported in the TC‐type EPO associated with the TC season 1 year to a year and half just before an El Niño–Southern Oscillation event. The analysis here provides refined statistical distributions of extreme rainfall, and these can contribute to the revision of governmental definitions for weather disasters that are used in mitigation and response strategies.

Effect of metals on zooplankton abundance and distribution in the coast of southwestern Taiwan - Yun-Ru Ju; Wen-Tseng Lo; Chih-Feng Chen; Chiu-Wen Chen; Zhi-Ling Huang; Cheng-Di Dong (Environmental Science and Pollution Research, 2019)

Three new labdane-type diterpenoids from Callicarpa macrophylla Vahl. - Zhen-Hui Wang; Huan-Jun Xu; Yang-Yang Zhai; Lan-Ping Yang; Qiang Li; Mei Huang; Xing-Ying Chen; Wen-Kui Zhang; Yue-Li Meng; Qing-Ling Zhang; Chao Niu; Yan-Ru Zhang (Natural Product Research, 2019)

A tree-ring–based summer (June–July) minimum temperature reconstruction for the western Kunlun Mountains since AD 1681 - Ru Huang; Haifeng Zhu; Eryuan Liang; Fayaz Asad; Jussi Grießinger (Theoretical and Applied Climatology, 2019)

A tree ring-based winter temperature reconstruction for the southeastern Tibetan Plateau since 1340 CE - Ru Huang; Haifeng Zhu; Eryuan Liang; Bo Liu; Jiangfeng Shi; Ruibo Zhang; Yujiang Yuan; Jussi Grießinger (Climate Dynamics, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Cloning and characterization of terpene synthase genes from Taiwan cherry - Kuan-Feng Huang; Chi-Hsiang Wen; Yi-Ru Lee; Fang-Hua Chu (Tree Genetics & Genomes, 2019)

Innovation-based urbanization: Evidence from 270 cities at the prefecture level or above in China - Lachang Lyu; Feixiang Sun; Ru Huang (Journal of Geographical Sciences, 2019)

Hepatitis C virus 3b strains in injection drug users in Guangdong Province, China, may have originated in Yunnan Province - Min Wang; Qiao Liao; Ru Xu; Dandan Song; Jieting Huang; Qingzhu You; Zhengang Shan; Ke Huang; Xia Rong; Yongshui Fu (Archives of Virology, 2019)

Identification and characterisation of a glycine-rich RNA-binding protein as an endogenous suppressor of RNA silencing from Nicotiana glutinosa - Xu Huang; Ru Yu; Wenjing Li; Liwei Geng; Xiuli Jing; Changxiang Zhu; Hongmei Liu (Planta, 2019)

First report of Stagonosporopsis citrulli causing gummy stem blight of watermelon in Taiwan - Chien-Jui Huang; Yi-Ru Lai (Journal of Plant Pathology, 2019)

Efficient generation of functional cardiomyocytes from human umbilical cord-derived virus-free induced pluripotent stem cells - Kai Hong Wu; Su Yun Wang; Qian Ru Xiao; Yu Yang; Ning Ping Huang; Xu Ming Mo; Jian Sun (Cell and Tissue Research, 2018)

First report of Acidovorax avenae subsp. avenae causing bacterial brown stripe disease of rice in Taiwan - Yi-Ru Lai; Chien-Jui Huang (Journal of Plant Pathology, 2018)

Combined prednisone and levothyroxine improve treatment of severe thrombocytopenia in hepatitis B with compensatory cirrhosis accompanied by subclinical and overt hypothyroidism - Jing Xue; Ru Feng; Haixia Fu; Qian Jiang; Hao Jiang; Jing Lu; Hui Liu; Jingwen Wang; Ting Niu; Xin Wang; Yandi Xie; Hao Wang; et al. (Science China Life Sciences, 2018)

Alternations of Metabolic Profile and Kynurenine Metabolism in the Plasma of Parkinson’s Disease - Kuo-Hsuan Chang; Mei-Ling Cheng; Hsiang-Yu Tang; Cheng-Yu Huang; Yih-Ru Wu; Chiung-Mei Chen (Molecular Neurobiology, 2018)

Hyperelastic Mechanical Properties of Ex Vivo Normal and Intrauterine Growth Restricted Placenta - Shier Nee Saw; Jess Yi Ru Low; May Han Huang Ong; Yu Wei Poh; Citra Nurfarah Zaini Mattar; Arijit Biswas; Choon Hwai Yap (Annals of Biomedical Engineering, 2018)

Characteristics and mechanisms of the diurnal variation of winter precipitation in Taiwan - Wan‐Ru Huang; Ya‐Hui Chang (International Journal of Climatology, 2018)
Using gridded precipitation data remapping from rain‐gauge observations of the time period of 2001–2015 winter months (December, January and February), this study examines the spatio‐temporal characteristics of the climatological diurnal winter precipitation in Taiwan. Our results show that the timings of the maximum values of the diurnal precipitation in Taiwan exhibit clear east–west regional differences, with night‐time maxima over eastern Taiwan but early morning maxima over western Taiwan. Analyses also show that the climatological characteristics of diurnal winter precipitation documented in this study are not controlled by some unusual, heavy precipitation events and can be seen as the common features. By examining the changes in meteorological variables (including winds, relative humidity and temperature) extracted from the in situ observations and the MERRA (Modern‐Era Retrospective Analysis for Research and Applications) reanalysis, this study further suggests that (a) the radiative cooling effect and (b) the surface wind convergence induced by the interaction between the local orography, the local land–sea breeze and the large‐scale diurnal circulation changes over the East Asian–western North Pacific (EAWNP) region are two of the possible formation mechanisms responsible for the spatio‐temporal differences of the climatological diurnal winter precipitation in Taiwan. This finding sheds light on the importance of understanding the role of the large‐scale diurnal circulation changes over the EAWNP region in modulating local diurnal precipitation properties during the winter months.

Soil physicochemical properties and vegetation structure along an elevation gradient and implications for the response of alpine plant development to climate change on the northern slopes of the Qilian Mountains - Yong-sheng Yang; Li Zhang; Hong-qin Li; Hui-dan He; Ya-xi Wei; Jin Luo; Guang-ru Zhang; Yu-ru Huang; Ying-nian Li; Hua-kun Zhou (Journal of Mountain Science, 2018)

Impact of boreal summer intra‐seasonal oscillations on warm season diurnal convection activity in Taiwan - Wan‐Ru Huang; Ya‐Hui Chang (International Journal of Climatology, 2018)
Diurnal convection (DC), which is characterized by rainy days with maximum rainfall during the afternoon without strong synoptic disturbances, is the most frequently observed weather system that affects local rainfall in Taiwan. In this study, we investigate the impact of boreal summer intra‐seasonal oscillations (BSISOs) on the modulation of warm season (May–September) DC activities in Taiwan. Our analyses focus on (1) identifying the relationships between changes in DC characteristics (e.g. DC days and the mean rainfall intensities on DC days) and the phase evolutions of two types of BSISOs (including the 30–60‐day ISO named BSISO1 and the 10–30‐day ISO named BSISO2) and (2) the related maintenance mechanisms. Analyses of DC days demonstrate that the contribution of DC days to the total quantity of rainy days in Taiwan generally reaches a maximum value when Taiwan is being modulated by intensified southwesterly winds, intensified local sea breeze circulations, and intensified local thermal instabilities (i.e. phase 3 of BSISO1 and phase 7 of BSISO2). Analyses of the mean rainfall intensities on DC days show that maximum values are generally reached when the moisture convergence line propagates northwards over Taiwan (i.e. phase 1 of BSISO1 and phase 3 of BSISO2). Further examinations indicate that the abovementioned findings are not dependent upon the strengths of the BSISOs.

Comparative chemical, taste, and functional components in different tissues of giant grouper ( Epinephelus lanceolatus ) - Chyuan-Yuan Shiau; Min-Hsien Hsu; Ann-Chang Cheng; Yu-Ru Huang (Journal of Aquatic Food Product Technology, 2018)

Investigating the composition characteristics of dissolved and particulate/colloidal organic matter in effluent-dominated stream using fluorescence spectroscopy combined with multivariable analysis - Min-Da Yu; Xiao-Song He; Bei-Dou Xi; Ru-Tai Gao; Xian-Wei Zhao; Hui Zhang; Cai-Hong Huang; Wenbing Tan (Environmental Science and Pollution Research, 2018)

Decadal fluctuations in the western Pacific recorded by long precipitation records in Taiwan - Wan-Ru Huang; S.-Y. Simon Wang; Biing T. Guan (Climate Dynamics, 2018)

Chemical Characteristics of Different Tissues of Spectacled Caiman ( Caiman crocodilus ) - Yu-Ru Huang; Yung-Hsiang Tsai; Ching-Lu Liu; Wei-Zong Syue; Yi-Cheng Su (Journal of Aquatic Food Product Technology, 2018)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Modulation of ARTS and XIAP by Parkin Is Associated with Carnosic Acid Protects SH-SY5Y Cells against 6-Hydroxydopamine-Induced Apoptosis - Ru-Huei Fu; Li-Chun Huang; Chia-Yuan Lin; Chia-Wen Tsai (Molecular Neurobiology, 2018)

New phenolic acids from Salvia yunnanensis C.H.Wright - Yun Yu; Yin-ru Wang; Zhen-huan Dong; Wei Li; Shu-Ming Li; Xue-feng Huang (Natural Product Research, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Erratum to: Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Future changes in propagating and non-propagating diurnal rainfall over East Asia - Wan-Ru Huang; S.-Y. Simon Wang (Climate Dynamics, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

Propofol attenuates H2O2-induced oxidative stress and apoptosis via the mitochondria- and ER-medicated pathways in neonatal rat cardiomyocytes - Xue-Ru Liu; Lu Cao; Tao Li; Lin-Lin Chen; Yi-Yan Yu; Wen-Jun Huang; Li Liu; Xiao-Qiu Tan (Apoptosis, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Adenosine A2A receptors in the olfactory bulb suppress rapid eye movement sleep in rodents - Yi-Qun Wang; Rui Li; Dian-Ru Wang; Yoan Cherasse; Ze Zhang; Meng-Qi Zhang; Oriana Lavielle; Kristopher McEown; Serge N. Schiffmann; Alban de Kerchove d’Exaerde; Wei-Min Qu; Michael Lazarus; et al. (Brain Structure and Function, 2017)

Inhibition of the Receptor for Advanced Glycation End-Products (RAGE) Attenuates Neuroinflammation While Sensitizing Cortical Neurons Towards Death in Experimental Subarachnoid Hemorrhage - Hua Li; Jia-Sheng Yu; Ding-Ding Zhang; Yi-Qing Yang; Li-Tian Huang; Zhuang Yu; Ru-Dong Chen; Hong-Kuan Yang; Chun-Hua Hang (Molecular Neurobiology, 2017)

An integrated earthquake early warning system and its performance at schools in Taiwan - Bing-Ru Wu; Nai-Chi Hsiao; Pei-Yang Lin; Ting-Yu Hsu; Chiou-Yun Chen; Shieh-Kung Huang; Hung-Wei Chiang (Journal of Seismology, 2017)

Dynamic quantitative proteomics characterization of TNF-α-induced necroptosis - Yang Wang; Zhi-Hao Huang; Yang-Jia Li; Gui-Wei He; Ru-Yuan Yu; Jie Yang; Wan-Ting Liu; Bin Li; Qing-Yu He (Apoptosis, 2016)

Salicylic acid-induced antioxidant protection against low temperature in cold-hardy winter wheat - Jing Yu; Jing Cang; Yanping Li; Ru Huang; Qiuwei Lu; Xiutian Wang; Lijie Liu; Qinghua Xu; Kejian Zhang (Acta Physiologiae Plantarum, 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Influence of Soluplus on Solid-State Properties and Physical Stability of Indomethacin-Saccharin Co-crystal Formation Prepared by Air-Drying Process - Shan-Yang Lin; Hong-Liang Lin; Ying-Ting Chi; Ru-Ying Hung; Yu-Ting Huang; Wei-Hsien Hsieh; Chi-Yu Kao (Journal of Pharmaceutical Innovation, 2016)

Fast Marching and Runge–Kutta Based Method for Centreline Extraction of Right Coronary Artery in Human Patients - Hengfei Cui; Desheng Wang; Min Wan; Jun-Mei Zhang; Xiaodan Zhao; Ru San Tan; Weimin Huang; Wei Xiong; Yuping Duan; Jiayin Zhou; Tong Luo; Ghassan S. Kassab; et al. (Cardiovascular Engineering and Technology, 2016)

Genetic Diversity and Population Structure Patterns in Chinese Cherry (Prunus pseudocerasus Lindl) Landraces - Tao Chen; Xiao-jiao Huang; Jing Zhang; Qing Chen; Yin Liu; Hao-ru Tang; Dong-ming Pan; Xiao-rong Wang (Plant Molecular Biology Reporter, 2016)

Evaluating the impacts of cumulus, land surface and ocean surface schemes on summertime rainfall simulations over East-to-southeast Asia and the western north Pacific by RegCM4 - Yu-Bin Li; Chi-Yung Tam; Wan-Ru Huang; Kevin K. W. Cheung; Zhiqiu Gao (Climate Dynamics, 2016)

The rural carbonaceous aerosols in coarse, fine, and ultrafine particles during haze pollution in northwestern China - Chong-Shu Zhu; Jun-Ji Cao; Chuen-Jinn Tsai; Zhen-Xing Shen; Sui-Xin Liu; Ru-Jin Huang; Ning-ning Zhang; Ping Wang (Environmental Science and Pollution Research, 2016)

Deficient and excess dietary selenium levels affect growth performance, blood cells apoptosis and liver HSP70 expression in juvenile yellow catfish Pelteobagrus fulvidraco - Jun-Ru Hu; Yan-Hua Huang; Guo-Xia Wang; Ying-Xia Wu; Jian-An Xian; An-Li Wang; Jun-Ming Cao (Fish Physiology and Biochemistry, 2016)

Isolation and characterization of collagens from the skin of giant grouper ( Epinephelus lanceolatus ) - Cheng-Hong Hsieh; Chyuan-Yuan Shiau; Yi-Cheng Su; Yi-Han Liu; Yu-Ru Huang (Journal of Aquatic Food Product Technology, 2016)

Changes in Biochemical Compositions and Quality of White Shrimp ( Litopenaeus vannamei ) During Storage - Yu-Ru Huang; Mirtala Francisca Guevara Zelaya; Chyuan-Yuan Shiau (Journal of Aquatic Food Product Technology, 2016)

Cloning, molecular characterization and functional analysis of a putative R2R3-MYB transcription factor of the phenolic acid biosynthetic pathway in S. miltiorrhiza Bge. f. alba - Gangping Hao; Xingyu Jiang; Lei Feng; Ru Tao; Yanling Li; Luqi Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Di-(2-ethylhexyl) phthalate accelerates atherosclerosis in apolipoprotein E-deficient mice - Jin-Feng Zhao; Sheng-Huang Hsiao; Ming-Hua Hsu; Kuan-Chuan Pao; Yu Ru Kou; Song-Kun Shyue; Tzong-Shyuan Lee (Archives of Toxicology, 2016)

Identification of geranylgeranyl diphosphate synthase genes from Tripterygium wilfordii - Meng Zhang; Ping Su; Yong-Jin Zhou; Xiu-Juan Wang; Yu-Jun Zhao; Yu-Jia Liu; Yu-Ru Tong; Tian-Yuan Hu; Lu-Qi Huang; Wei Gao (Plant Cell Reports, 2015)

Expression of ethylene biosynthetic and signaling genes in relation to ripening of banana fruit after cold storage - Keqian Hong; Jianghui Xie; Ru Zou; Ezhen Zhang; Min Xin; Maokang Huang; Quanguang He (Acta Physiologiae Plantarum, 2015)

Invasive fungal infection in allogeneic hematopoietic stem cell transplant recipients: single center experiences of 12 years - Ji-min Shi; Xu-ying Pei; Yi Luo; Ya-min Tan; Ru-xiu Tie; Jing-song He; Wei-yan Zheng; Jie Zhang; Zhen Cai; Mao-fang Lin; He Huang (Journal of Zhejiang University-SCIENCE B, 2015)

Tree bark as a biomonitor for the determination of polychlorinated biphenyls and polybrominated diphenyl ethers from Southern Jiangsu, China: levels, distribution, and possible sources - Li Zhou; Liang Dong; Ye-Ru Huang; Shuang-Xin Shi; Li-Fei Zhang; Xiu-Lan Zhang; Wen-Long Yang (Environmental Monitoring and Assessment, 2015)

Detection of gas hydrate sediments using prestack seismic AVA inversion - Ru-Wei Zhang; Hong-Qi Li; Bao-Jin Zhang; Han-Dong Huang; Peng-Fei Wen (Applied Geophysics, 2015)

Changes of polybrominated diphenyl ethers and polychlorinated biphenyls in surface soils from urban agglomeration of the Yangtze River Delta, in China between 2003 and 2012 - Shuang-Xin Shi; Ye-Ru Huang; Li Zhou; Li-Fei Zhang; Liang Dong; Wen-Long Yang; Xiu-Lan Zhang (Environmental Science and Pollution Research, 2015)

Combined characteristics of drought on multiple time scales in Huang-Huai-Hai River basin - Ru Huang; Denghua Yan; Shaohua Liu (Arabian Journal of Geosciences, 2015)

Trends in pre‐summer frontal and diurnal rainfall activities during 1982–2012 over Taiwan and Southeast China: characteristics and possible causes - Wan‐Ru Huang; Kuan‐Chieh Chen (International Journal of Climatology, 2015)

Characterization of 26 deletion CNVs reveals the frequent occurrence of micro-mutations within the breakpoint-flanking regions and frequent repair of double-strand breaks by templated insertions derived from remote genomic regions - Ye Wang; Peiqiang Su; Bin Hu; Wenjuan Zhu; Qibin Li; Ping Yuan; Jiangchao Li; Xinyuan Guan; Fucheng Li; Xiangyi Jing; Ru Li; Yongling Zhang; et al. (Human Genetics, 2015)

Comparative pharmacokinetics of oxytetracycline in blunt-snout bream (Megalobrama amblycephala) with single and multiple-dose oral administration - Ru-Qin Li; Yu-Wei Ren; Jing Li; Can Huang; Jun-hui Shao; Xiao-Xuan Chen; Zhi-Xin Wu (Fish Physiology and Biochemistry, 2015)

CIC-3 chloride channel blockade protects mouse photoreceptor-derived 661W cells against ischemia-reperfusion-induced injury in vitro - Shi Wei Huang; Yuan Yin; Ya Juan Zheng; Ya Ru Dong (Molecular & Cellular Toxicology, 2015)

Studies on mitogen-activated protein kinase signaling pathway in the alveolar macrophages of chronic bronchitis rats - Yan Huang; Xiao-Ming Meng; Guo-Lin Jiang; Ya-Ru Yang; Juan Liu; Xiong-Wen Lv; Jun Li (Molecular and Cellular Biochemistry, 2015)

Increased prevalence of hepatitis C virus subtype 6a in China: a comparison between 2004–2007 and 2008–2011 - Xia Rong; Ru Xu; Huaping Xiong; Min Wang; Ke Huang; Qiuyu Chen; Chengyao Li; Qiao Liao; Jieting Huang; Wenjie Xia; Guangping Luo; Xin Ye; et al. (Archives of Virology, 2014)

Efficacy of a high-growth reassortant H1N1 influenza virus vaccine against the classical swine H1N1 subtype influenza virus in mice and pigs - Feng Wen; Hai Yu; Fu-ru Yang; Meng Huang; Sheng Yang; Yan-Jun Zhou; Ze-Jun Li; Guang-Zhi Tong (Archives of Virology, 2014)

Impact of land–sea breezes at different scales on the diurnal rainfall in Taiwan - Wan-Ru Huang; Shih-Yu Wang (Climate Dynamics, 2014)

Occurrence, sources, and ecological risks of PBDEs, PCBs, OCPs, and PAHs in surface sediments of the Yangtze River Delta city cluster, China - Ting Zhang; Wen-Long Yang; She-Jun Chen; Dian-Long Shi; Hu Zhao; Yi Ding; Ye-Ru Huang; Nan Li; Yue Ren; Bi-Xian Mai (Environmental Monitoring and Assessment, 2014)

Spatial-temporal scales of Green Island wake due to passing of the Kuroshio current - Shih-Jen Huang; Chung-Ru Ho; Sheng-Lin Lin; Shin-Jye Liang (International Journal of Remote Sensing, 2014)

Seasonal variations of monocarbonyl and dicarbonyl in urban and sub-urban sites of Xi’an, China - K. F. Ho; Steven Sai Hang Ho; W. T. Dai; J. J. Cao; Ru-Jin Huang; Linwei Tian; W. J. Deng (Environmental Monitoring and Assessment, 2014)

Dynamical downscaling forecasts of Western North Pacific tropical cyclone genesis and landfall - Wan-Ru Huang; Johnny C. L. Chan (Climate Dynamics, 2014)

Characterization of S-(+)-linalool synthase from several provenances of Cinnamomum osmophloeum - Yan-Liang Lin; Yi-Ru Lee; Wen-Ke Huang; Shang-Tzen Chang; Fang-Hua Chu (Tree Genetics & Genomes, 2014)

SNP and haplotype analysis reveal IGF2 variants associated with growth traits in Chinese Qinchuan cattle - Yong-Zhen Huang; Zhao-Yang Zhan; Xin-Yi Li; Sheng-Ru Wu; Yu-Jia Sun; Jing Xue; Xian-Yong Lan; Chu-Zhao Lei; Chun-Lei Zhang; Yu-Tang Jia; Hong Chen (Molecular Biology Reports, 2014)

Circulating microparticles in patients with coronary heart disease and its correlation with interleukin-6 and C-reactive protein - Ying Cui; Lihui Zheng; Ming Jiang; Ru Jia; Xiao Zhang; Qishan Quan; Guiqin Du; Dongjin Shen; Xiaodan Zhao; Wenying Sun; Hongwei Xu; Lijuan Huang (Molecular Biology Reports, 2013)

Isolation and characterization of a novel PDR-type ABC transporter gene PgPDR3 from Panax ginseng C.A. Meyer induced by methyl jasmonate - Ru Zhang; Jingjia Huang; Jie Zhu; Xiaolei Xie; Qin Tang; Xianghui Chen; Jun Luo; Zhiyong Luo (Molecular Biology Reports, 2013)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

Genetic diversity and population structure of Chinese Cherry revealed by chloroplast DNA trnQ-rps16 intergenic spacers variation - Tao Chen; Xiao-rong Wang; Hao-ru Tang; Qing Chen; Xiao-jiao Huang; Jiao Chen (Genetic Resources and Crop Evolution, 2013)

Inhibition of formyl peptide-stimulated phospholipase D activation by Fal-002-2 via blockade of the Arf6, RhoA and protein kinase C signaling pathways in rat neutrophils - Ya-Ru Tsai; Li-Jiau Huang; Hui-Yi Lin; Yun-Jie Hung; Miau-Rong Lee; Sheng-Chu Kuo; Mei-Feng Hsu; Jih-Pyang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Toxicokinetics of tilapia following high exposure to waterborne and dietary copper and implications for coping mechanisms - Jeng-Wei Tsai; Yun-Ru Ju; Ying-Hsuan Huang; Yue-Sun Deng; Wei-Yu Chen; Chin-Ching Wu; Chung-Min Liao (Environmental Science and Pollution Research, 2013)

Regional climate simulations of summer diurnal rainfall variations over East Asia and Southeast China - Wan-Ru Huang; Johnny C. L. Chan; Andie Y. M. Au-Yeung (Climate Dynamics, 2013)

Molecular cloning, expression profiles and subcellular localization of cyclin B in ovary of the mud crab, Scylla paramamosain - Wen-Xing Li; Hui-Yang Huang; Jing-Ru Huang; Jin-Jin Yu; Jun Ma; Hai-Hui Ye (Genes & Genomics, 2013)

Spatio-temporal variation of landscape heterogeneity under influence of human activities in Xiamen City of China in recent decade - Yixiong Huang; Xiuqin Yin; Gongfu Ye; Jiemin Lin; Ru Huang; Na Wang; Liang Wang; Yue Sun (Chinese Geographical Science, 2013)

A Mucormycosis Case in a Cirrhotic Patient Successfully Treated with Posaconazole and Review of Published Literature - Shang-Yi Lin; Po-Liang Lu; Kun-Bow Tsai; Chun-Yu Lin; Wei-Ru Lin; Tun-Chieh Chen; Ya-Ting Chang; Chung-Hao Huang; Chi-Yu Chen; Chung-Chih Lai; Yen-Hsu Chen (Mycopathologia, 2012)

Erratum to: Inflammation in Patients with Schizophrenia: The Therapeutic Benefits of Risperidone Plus Add-On Dextromethorphan - Shiou-Lan Chen; Sheng-Yu Lee; Yun-Hsuan Chang; Shih-Heng Chen; Chun-Hsieh Chu; Nian-Sheng Tzeng; I-Hui Lee; Po-See Chen; Tzung Lieh Yeh; San-Yuan Huang; Yen-Kuang Yang; Ru-Band Lu; et al. (Journal of Neuroimmune Pharmacology, 2012)

Co-variability of poleward propagating atmospheric energy with tropical and higher-latitude climate oscillations - Wan-Ru Huang; Tsing-Chang Chen; Shih-Yu Wang (Climate Dynamics, 2012)

Seasonal variation of diurnal and semidiurnal rainfall over Southeast China - Wan-Ru Huang; Johnny C. L. Chan (Climate Dynamics, 2012)

Urban hierarchy of innovation capability and inter-city linkages of knowledge in post-reform China - Lachang Lu; Ru Huang (Chinese Geographical Science, 2012)

Inflammation in Patients with Schizophrenia: The Therapeutic Benefits of Risperidone Plus Add-On Dextromethorphan - Shiou-Lan Chen; Sheng-Yu Lee; Yun-Hsuan Chang; Shih-Heng Chen; Chun-Hsieh Chu; Nian-Sheng Tzeng; I-Hui Lee; Po-See Chen; Tzung Lieh Yeh; San-Yuan Huang; Yen-Kuang Yang; Ru-Band Lu (Journal of Neuroimmune Pharmacology, 2012)

Culture-independent characterization of the autochthonous gut microbiota of grouper Epinephelus coioides following the administration of probiotic Enterococcus faecium - Yun-Zhang Sun; Hong-Ling Yang; Ru-Long Ma; Kun-Peng Huang; Ji-Dan Ye (Aquaculture International, 2012)

Effect of Sulforaphane on Growth Inhibition in Human Brain Malignant Glioma GBM 8401 Cells by Means of Mitochondrial- and MEK/ERK-Mediated Apoptosis Pathway - Tzuu-Yuan Huang; Weng-Cheng Chang; Miin-Yau Wang; Yun-Ru Yang; Yi-Chiang Hsu (Cell Biochemistry and Biophysics, 2012)

Observational and supportive modelling analyses of winter precipitation change in China over the last half century - Robert R. Gillies; Shih‐Yu Wang; Wan‐Ru Huang (International Journal of Climatology, 2012)
Overall increasing trends in annual precipitation and widespread warming over China have been documented. During the winter months in southeast China, where snow is commonplace but rarely accumulates, the climatological 0 °C surface isotherm generally defines the southern boundary of the snowfield. Therefore, a warming climate will: (a) modify the southern boundary of the snowfield; and (b) potentially alter the snow‐rain ratio. Using recently released daily precipitation from the Asian Precipitation‐Highly Resolved Observational Data Integration Towards Evaluation (APHRODITE) and temperature observations from the ERA‐40/Interim Reanalyses, this study investigated historical winter precipitation changes in China. Since snowfall observations were largely unavailable for southeast China, snowfall amounts were estimated using a rain‐snow threshold temperature (RST) method which was subsequently verified by in situ and satellite observations of snow depth, snow cover, and snow water equivalent (SWE). The composite analysis reveals a decrease in snowfall totals which are accompanied by an increase in rainfall; this change corresponds with the northward retreat of the 0 °C surface isotherm and the snow‐rain ratio. Atmospheric circulation analysis indicated lower tropospheric warming with increased moisture over southeast China, consistent with previous studies. Moreover, we observed an increase in the convergence of water vapour flux which sustains the increase in precipitation; this is accompanied by the suppression of snowfall due to the lower tropospheric warming. An additional analysis employed to further substantiate the RST method was undertaken by modelling the snow‐rain ratio with the Weather Research and Forecasting (WRF) Model. The results were in agreement with those estimated from the observations. Copyright © 2011 Royal Meteorological Society

Polycyclic aromatic hydrocarbons in household dust near diesel transport routes - Chung-Yih Kuo; Heng-Chun Chen; Fang-Ching Cheng; Li-Ru Huang; Po-Shan Chien; Jing-Ya Wang (Environmental Geochemistry and Health, 2012)

Variability of sea surface temperature and warm pool area in the South China Sea and its relationship to the western Pacific warm pool - Chun-Yi Lin; Chung-Ru Ho; Quanan Zheng; Shih-Jen Huang; Nan-Jung Kuo (Journal of Oceanography, 2011)

Study of prestack elastic parameter consistency inversion methods - Han-Dong Huang; Ru-Wei Zhang; Guo-Qiang Shen; Fei Guo; Jia-Bei Wang (Applied Geophysics, 2011)

Discrepancies between global reanalyses and observations in the interdecadal variations of Southeast Asian cold surge - Wan‐Ru Huang; Shih‐Yu Wang; Johnny C. L. Chan (International Journal of Climatology, 2011)
The Siberian High (SH) is an important part of the East Asian winter monsoon (EAWM) and is closely linked to cold surges. Previous studies revealed a pronounced decline in the strength of the SH during the late 20th century accompanied with a coherent decrease in the frequency of cold surges. However, studies using different data sets yielded different behaviour of the trends. Here we examine the interdecadal variations of the SH and cold surges deduced from six modern global reanalysis data sets. Discrepancies in such variations are found between the reanalysis data sets and observations as well as among different reanalysis data sets. Such discrepancies contribute to inconsistent interdecadal variations of the cold surge frequency in different reanalysis data sets. Potential causes of this situation are discussed. Copyright © 2010 Royal Meteorological Society

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

Lipopolysaccharide-stimulated activation of murine DC2.4 cells is attenuated by n-butylidenephthalide through suppression of the NF-κB pathway - Ru-Huei Fu; Horng-Jyh Hran; Ching-Liang Chu; Chin-Mao Huang; Shih-Ping Liu; Yu-Chi Wang; Ya-Hsien Lin; Woei-Cherng Shyu; Shinn-Zong Lin (Biotechnology Letters, 2011)

Loudness dependence of auditory evoked potentials (LDAEP) correlates with the availability of dopamine transporters and serotonin transporters in healthy volunteers—a two isotopes SPECT study - I Hui Lee; Yen Kuang Yang; Po See Chen; Hui Chun Huang; Tzung Lieh Yeh; Ru-Band Lu; Nan-Tsing Chiu; Wei Jen Yao; Shih-Hsien Lin (Psychopharmacology, 2011)

Asterotremella meifongana sp. nov. and Asterotremella nantouana sp. nov., two anamorphic basidiomycetous yeasts isolated from soil and mushrooms - Yi-Ru Liu; Li-Ying Huang; Suh-Shen Young; Chin-Feng Chang; Ching-Fu Lee (Antonie van Leeuwenhoek, 2011)

Exploring the molecular mechanisms of OSU-03012 on vascular smooth muscle cell proliferation - Wei-Wen Kuo; Jing-Ru Weng; Chih-Yang Huang; Chang-Hai Tsai; Wei-Hung Liu; Cheng-Hao Wen; Shih-Chang Tsai; Chieh-Hsi Wu (Molecular and Cellular Biochemistry, 2010)

Simulation of organic carbon dynamics at regional scale for paddy soils in China - Xue-Zheng Shi; Ru-Wei Yang; David C. Weindorf; Hong-Jie Wang; Dong-Sheng Yu; Yao Huang; Xian-Zhang Pan; Wei-Xia Sun; Li-Ming Zhang (Climatic Change, 2010)

Estimates of individuals exposed to human metapneumovirus in a community-based Taiwanese population in 1999 - Chung-Guei Huang; Kuo-Chien Tsao; Tzou-Yien Lin; Yhu-Chering Huang; Li-Ang Lee; Tzu-Hou Chen; Ya-Ling Huang; Shin-Ru Shih (Archives of Virology, 2010)

SCA8 repeat expansion: large CTA/CTG repeat alleles in neurological disorders and functional implications - Yih-Ru Wu; I-Cheng Chen; Bing-Wen Soong; Shih-Huan Kao; Ghin-Chueh Lee; Shu-Yi Huang; Hon-Chung Fung; Guey-Jen Lee-Chen; Chiung-Mei Chen (Human Genetics, 2009)

Exsolution lamellae in a clinopyroxene megacryst aggregate from Cenozoic basalt, Leizhou Peninsula, South China: petrography and chemical evolution - Xiao-Long Huang; Yi-Gang Xu; Ching-Hua Lo; Ru-Cheng Wang; Chuan-Yong Lin (Contributions to Mineralogy and Petrology, 2007)

PaCDPK1, a gene encoding calcium-dependent protein kinase from orchid, Phalaenopsis amabilis, is induced by cold, wounding, and pathogen challenge - Tsung-Mu Tsai; Ying-Ru Chen; Tien-Wen Kao; Wen-Su Tsay; Chiou-Ping Wu; Ding-Ding Huang; Wen-Huei Chen; Ching-Chun Chang; Hao-Jen Huang (Plant Cell Reports, 2007)

Nematicidal Resorcylides from the Aquatic Fungus Caryospora callicarpa YMF1.01026 - Jinyan Dong; Yanhui Zhu; Hongchuan Song; Ru Li; Hongping He; Haiyang Liu; Rong Huang; Yongping Zhou; Le Wang; Yi Cao; Keqin Zhang (Journal of Chemical Ecology, 2007)

Effect of banning vancomycin analogue avoparcin on vancomycin‐resistant enterococci in chicken farms in Taiwan - Tsai‐Ling Lauderdale; Yih‐Ru Shiau; Hui‐Ying Wang; Jui‐Fen Lai; I‐Wen Huang; Pei‐Chen Chen; Hong‐Yi Chen; Shiow‐Suey Lai; Ya‐Fang Liu; Monto Ho (Environmental Microbiology, 2007)
Summary Avoparcin, a vancomycin analogue, was banned as a feed additive in Taiwan in 2000. A nationwide surveillance was conducted to study the prevalence of vancomycin‐resistant enterococci (VRE) on chicken farms between 2000 and 2003. Among the 1021 E. faecalis and 967 E. faecium isolates studied, resistance to tetracycline, erythromycin, high‐level aminoglycosides, ciprofloxacin and chloramphenicol either increased or remained high except vancomycin. The proportion of VRE decreased, between 2000 and 2003, from 13.7% (22/161) to 3.7% (11/299) for E. faecalis , and 3.4% (4/119) to 0% (0/300) for E. faecium . Only 8.8% (7/80) of the chicken farms surveyed harboured VRE in 2003 compared with 25% (15/60) in 2000. All VRE were resistant to tetracycline and erythromycin. All VRE possess the vanA gene but nearly all (79 of 83 isolates) were susceptible to teicoplanin, indicating VanB phenotype. Some clones were detected from different farms in various regions over the years. We conclude that the frequency of VRE in chicken farms decreased in association with a ban on avoparcin; and the continued presence of VRE may be due to the ability of some strains to persist in the farms, transfer of vancomycin resistance determinants or co‐selection by the continued use of other antibiotics.

Application of Bayesian Regularized BP Neural Network Model for Trend Analysis, Acidity and Chemical Composition of Precipitation in North Carolina - Min Xu; Guangming Zeng; Xinyi Xu; Guohe Huang; Ru Jiang; Wei Sun (Water, Air, & Soil Pollution, 2006)

Renal Tubule-Specific Expression and Urinary Secretion of Human Growth Hormone: A Kidney-Based Transgenic Bioreactor - Xinhua Zhu; Jin Cheng; Liwei Huang; Jin Gao; Zhong-Ting Zhang; Joanne Pak; Xue-Ru Wu (Transgenic Research, 2003)

Seasonal modulated intraseasonal oscillations in a GCM simulation - Jian-Ping Huang; Han-Ru Cho (International Journal of Climatology, 1998)